Ultra-high molecular weight polymers and methods of making and using same
By performing photoinitiator polymerization under reverse phase fine emulsion conditions, the synthesis of branched or hyperbranched water-soluble polymers with molecular weights of about 10kDa to 10,000kDa solves the problem of molecular weight and structure of mucin in the cornea and tear film of the eye, and improves mucin hydration and rheology, and improves eye health and durability.
Patent Information
- Application Number
- CN202380046711.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-14
- Filing Date
- 2023-04-28
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art is difficult to effectively solve the molecular weight and structural problems of mucin in the cornea and tear film of the eyes, resulting in limited eye health, durability and comfort.
Photoinitiator polymerization is performed under reverse phase fine emulsion conditions to synthesize branched or hyperbranched water-soluble polymers with molecular weights of about 10 kDa to 10,000 kDa. By polymerizing the main chain unit and the mucin binding unit, a polymer with improved mucin hydration and rheology is formed.
Improved hydration and rheology of mucin, enhanced homeostasis and transparency of the eye surface, provided better physical barrier protection, and improved eye health and durability.
Smart Images

Figure CN119731223A_ABST
Abstract
Description
[0001] Priority claim of related application
[0002] This application claims priority to co-pending U.S. Provisional Application Serial No. 63 / 336,733, filed on April 29, 2022, entitled “Ultra-High Molecular Weight Polymers and Methods of Making and Using Them”, which is incorporated herein by reference in its entirety. In addition, this application claims priority to co-pending U.S. Provisional Application Serial No. 63 / 368,404, filed on July 14, 2022, entitled “Ultra-High Molecular Weight Polymers and Methods of Making and Using Them”, which is incorporated herein by reference in its entirety. Background Art
[0003] The eye's first line of defense against the external environment is a thin layer of moist epithelial cells stratified on the corneal surface, protected by an aqueous and mucous tear film. The health, durability, and comfort of the eye are inextricably linked to the ability of these epithelial cells to produce mucins to form the glycocalyx and stabilize the tear film. Ocular mucins contribute to ocular surface homeostasis, maintain corneal and tear film transparency, and provide a physical barrier that protects against foreign debris (e.g., pathogens, toxins, and particles) while allowing the rapid passage of selected gases, fluids, ions, and nutrients.
[0004] The cornea and conjunctiva express lower molecular weight transmembrane mucins (MUC1, MUC4, MUC16, and MUC20) that anchor secretory mucins and gel-forming mucins (MUC2, MUC5AC) produced by goblet cells found in the conjunctival epithelium. The mucins (MUC1, MUC2, MUC4, MUC5AC, and MUC16) present in the tear film together form a gel layer that serves to maintain hydration and transparency of the ocular surface, provide lubrication, and resist adhesion between the corneal and conjunctival epithelium during blinking.
[0005] These mucins form a hydrogel network spanning the gel, called a glycocalyx, which stabilizes the tear film and prevents drying. This gel network is cross-linked primarily by physical cross-links, rather than chemical cross-links. Crucially, the weak physical cross-links and large mesh size of the mucin gel result in a surface with inherently low shear stress and low yield stress during sliding. When the yield stress is exceeded (for example, during blinking), the physical cross-links dynamically break and heal. The gel spanning the mucin network acts like a mechanical fuse, limiting the level of potentially damaging stress that could be transmitted to the underlying epithelial cells.
[0006] Table 1 lists the mucins found in the ocular environment. This extensive array of mucins, as a system, produces a gel-spanning network with finite yield stress, shear thinning, and maintains a smooth and uniform film thickness at optical interfaces. Corneal epithelial cells do not form gel-forming mucins and soluble mucins.
[0007]
[0008] The eye rarely rests during wakefulness, blinking about 20,000 times a day. During a blink, the eyelid wiper accelerates to a maximum speed of about 100 mm / s, approaches the lower eyelid, and then retracts; the entire process occurs in about 100 milliseconds. The contact pressure exerted by the eyelid on the cornea during this activity has not been directly measured, but is thought to be about 1-5 kPa.
[0009] The inset of Figure 1 shows a schematic diagram of the corneal epithelium, tear film, mucins associated with the ocular surface (including the intercellular secretory mucin MUC20), and waxy lipid layers. The tear film (approximately 5 μm thick) covers the corneal epithelial cells (approximately 55 μm thick) on the ocular surface. Lipid rafts (50-100 nm thick) are produced by the meibomian glands at the eyelid margins and are thought to prevent tear film evaporation and prevent fine dust and debris from entering the intraocular environment. The inset also shows the large molecular weight and complex structure of secretory and gel-forming mucins and soluble tear film mucins. The ultrastructure of the corneal epithelium and the microvilli detail on the surface of the stratified squamous epithelium increase the surface area of the secretory membrane-bound mucins MUC1, MUC4, and MUC16. These mucins together anchor secretory and soluble mucins to form a biopolymer hydrogel called glycocalyx that stabilizes the tear film and prevents drying. The discomfort of dry eye may have underlying causes, including frictional shear stress that exceeds physiological levels that can be well tolerated. The quality of the tear film is critical for both applications. Summary of the invention
[0010] The present disclosure provides compositions comprising at least one water-soluble polymer having a molecular weight of about 10 kilodaltons (kDa) to 10,000 kDa, methods of making the water-soluble polymers, structures having a distribution of the water-soluble polymers, and methods of using the same. The present disclosure provides branched and hyperbranched water-soluble polymers and methods of making branched and hyperbranched water-soluble polymers.
[0011] The present disclosure provides a method for preparing a first water-soluble polymer, comprising: polymerizing a backbone unit and at least one mucin binding unit under inverse miniemulsion conditions to form the first water-soluble polymer polymerized using a photoinitiator. In one aspect, the method is a catalyst-free multiphase process mediated by low-intensity ultraviolet irradiation.
[0012] The present disclosure provides a synthetic method for preparing a branched or hyperbranched first water-soluble polymer, comprising: polymerizing a backbone unit and at least one mucin binding unit to form a branched or hyperbranched first water-soluble polymer, wherein the branched or hyperbranched first water-soluble polymer has a molecular weight of about 10 kDa to 10,000 kDa, wherein the branched or hyperbranched first water-soluble polymer comprises a plurality of backbone units and at least one first type of mucin binding unit, wherein the backbone unit comprises greater than 50% of the first water-soluble polymer based on molecular weight, wherein the first type of mucin binding unit accounts for at most 50% of 1 unit of the first water-soluble polymer based on molecular weight, wherein the first type of mucin binding unit is functionalized so that the water-soluble polymer has a property of changing hydration, rheology, or both of a mucin polymer, a second water-soluble polymer, or a combination thereof, wherein changing hydration, rheology, or both is achieved by mucoadhesion, mucosal plasticity, mucosal integration, or a combination thereof.
[0013] The present disclosure provides a composition comprising a first branched or hyperbranched water-soluble polymer having a molecular weight of about 10 kDa to 10,000 kDa, wherein the first branched or hyperbranched water-soluble polymer comprises a plurality of backbone units and at least one first type of mucin-binding unit, wherein the backbone units comprise greater than 50% of the first branched or hyperbranched water-soluble polymer based on the molecular weight, wherein when forming the branched or hyperbranched first water-soluble polymer, the backbone units are the reaction product of a multifunctional water-soluble monomer and a water-soluble monofunctional unit, wherein the multifunctional water-soluble monomer The mole % of the monofunctional water-soluble monomer is less than 1%, wherein the first type of mucin binding unit accounts for up to 50% of one unit of the first branched or hyperbranched water-soluble polymer based on molecular weight, wherein the first type of mucin binding unit is functionalized so that the first branched or hyperbranched water-soluble polymer has the property of changing the hydration, rheology, or both of the mucin polymer, the second water-soluble polymer, or a combination thereof, wherein changing the hydration, rheology, or both is achieved by mucoadhesion, mucoadhesion, mucoadhesion, mucoadhesion, or a combination thereof.
[0014] The present disclosure provides a composition comprising a first branched or hyperbranched water-soluble polymer having a molecular weight of about 10 kDa to 10,000 kDa, wherein the first branched or hyperbranched water-soluble polymer comprises a plurality of backbone units and at least one first type of mucin-binding unit, wherein the backbone unit comprises greater than 50% of the first branched or hyperbranched water-soluble polymer based on molecular weight, wherein the backbone unit is the reaction product of a first initiating monomer and a second initiating monomer, wherein the first initiating monomer and the second initiating monomer contain a vinyl group and a group capable of initiating polymerization or capable of being converted into a group capable of initiating polymerization, wherein the first type of mucin-binding unit accounts for at most 50% of 1 unit of the first branched or hyperbranched water-soluble polymer based on molecular weight, wherein the first type of mucin-binding unit is functionalized so that the first branched or hyperbranched water-soluble polymer has a property of changing the hydration, rheology, or both of the mucin polymer, the second water-soluble polymer, or a combination thereof, wherein changing the hydration, rheology, or both is achieved by mucoadhesion, mucosal plasticity, mucosal integration, or a combination thereof.
[0015] The present disclosure provides a composition comprising a first water-soluble polymer having a molecular weight of about 10 kDa to 10,000 kDa, wherein the first water-soluble polymer comprises a plurality of backbone units and at least one first type of mucin-binding unit, wherein the backbone units comprise greater than 50% of the first water-soluble polymer based on molecular weight, wherein the first type of mucin-binding unit comprises at most 50% of 1 unit of the first water-soluble polymer based on molecular weight, wherein the first type of mucin-binding unit is functionalized so that the first water-soluble polymer has a property of altering hydration, rheology, or both of a mucin polymer, a second water-soluble polymer, or a combination thereof, wherein altering hydration, rheology, or both is achieved by mucoadhesion, mucoadhesion, mucoadhesion, mucoadhesion, or a combination thereof; wherein the backbone units comprise monomeric units; The invention relates to a monomer unit and a copolymer comprising said monomer unit, wherein said monomer unit is selected from substituted acrylamide or substituted methacrylamide, or wherein said mucin binding unit comprises a monomer unit or a copolymer comprising said monomer unit, wherein said monomer unit is selected from: (4-((2-acrylamidoethyl)carbamoyl)-3-chlorophenyl)boric acid, (4-((2-acrylamidoethyl)carbamoyl)-3-fluorophenyl)boric acid, (4-((2-acrylamidoethyl)carbamoyl)-3-bromophenyl)boric acid, (4-((2-acrylamidoethyl)carbamoyl)-3-iodophenyl)boric acid, a monomer comprising one or more boronic acid groups, a monomer containing one or more disulfide forming groups, or a derivative of any of these groups, wherein said backbone unit is N-hydroxyethylacrylamide having the following structure: wherein n is 1-10, wherein R is a hydroxyl group, an amine group, a carboxylic acid group or a sulfonic acid group, and wherein R' is a C1-C18 straight chain or branched alkyl group. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The present disclosure may be better understood with reference to the following drawings.
[0017] Figure 1.1A A scheme for the DMA photoinitiator polymerization using iniferter 1 under inverse miniemulsion conditions is shown. Figure 1.1B A diagram showing the components of an inverse miniemulsion polymerization is shown.
[0018] Figure 1C shows Scheme A and Scheme B. Scheme A illustrates the photolytic bond cleavage of a universal photoinitiator (ZC(=S)SR). Scheme B illustrates the photoinitiated polymerization of N,N-dimethylacrylamide (DMA) using 2-(ethylthiocarbonylthiothio)propionic acid (iniferter 1) to produce poly(N,N-dimethylacrylamide) (PDMA).
[0019] Figure 1.2A Shown are photographs of emulsions formulated as described in Table 1 taken after sonication and before polymerization. Figure 1.2B DLS particle size distribution is shown, showing the number average hydrodynamic diameter (d N ), intensity average hydrodynamic diameter (d I ) and z-average hydrodynamic diameter (d z ). Figure 1.2C The size distribution of cross-linked PDMA particles (n=133) in TEM images is shown. D) TEM image of PDMA particles using MBA cross-linker.
[0020] Figure 1.3A Shown is the size exclusion chromatography (SEC) curve of PDMA prepared by reverse miniemulsion photoinitiator polymerization with molecular weights ranging from 119,000 to 1,210,000 Da. By reducing the polymerization temperature to 10°C, polymers with molecular weights up to 1,210,000 Da (red curve) can be obtained. Figure 1.3B A photograph of a post-polymerization DMA miniemulsion system in a 10-mL Schlenk flask is shown. When inverted, the solution flows easily. Figure 1.3C A photograph of DMA polymerization after polymerization in a 10-mL Schlenk flask in a homogeneous aqueous medium (5 M DMA in PB) is shown. The high viscosity solution flows very slowly when inverted.
[0021] Figure 1.4AThe SEC curve of DMA polymerization mediated by iniferter 1 under the conditions listed in Table 1 is shown, showing a trend of decreasing elution time with increasing polymerization time. Figure 1.4B The experimental and theoretical number average molecular weight (M n ) and the molar mass dispersion as a function of monomer conversion. Figure 1.4C A linear pseudo-first order kinetic plot is shown, indicating a constant free radical flux in the system. Figure 1.4D Particle size (d z ).
[0022] Figure 1.5A The structures of iniferters 1-4 are shown. Figure 1.5B The UV-visible absorption spectra and maximum absorbance (λ max ). Figure 1.5C Shown are the changes in UV absorbance of iniferters 1-4 in PB before and after addition of cyclohexane in the absence of UV light. Figure 1.5D Shown are changes in UV absorbance of iniferters 1–4 in PB after UV irradiation. Figure 1.5E Pseudo-first order kinetics are shown. Figure 1.5F The experimental molecular weight (M n ), the molecular weight (M n ) are plotted as a function of monomer conversion for polymerizations carried out using iniferters 1-4.
[0023] Figure 1.6A The SEC curves of PDMA and PDMA-b-PNMO mediated by iniferter 3 under the conditions shown in Table 1 are shown. n,exp =808,000Da,M n,theo =880,000Da, ) and NMO for chain extension, reaching a final conversion rate of about 99% within 4 hours (M n,exp =2,080,000,M n,theo =2,480,000, ). Figure 1.6B The z-average particle size (d) before initial polymerization, after DMA polymerization, after NMO / PB solution was added to PDMA miniemulsion, and after PDMA-b-NMO synthesis is shown. z ).
[0024] Figure 1.7A -D shows a time-controlled study of DMA polymerization using iniferter 1 under the reverse miniemulsion conditions of Table 1. Figure 1.7APseudo-first order kinetics and the change in monomer conversion over time during the on-off photocycle are shown. Figure 1.7B SEC curves are shown, indicating that the molecular weight increases with increasing monomer conversion. Figure 1.7C The experimental molecular weight and dispersity plotted as a function of monomer conversion are shown. n,exp It increases linearly with monomer conversion and the dispersion remains reasonable throughout the polymerization process. Figure 1.7D Shown is particle size plotted as a function of polymerization time throughout the on-off light cycle.
[0025] Figure 2.1A The reverse miniemulsion photoinitiator polymerization of N,N-dimethylacrylamide (DMA) in continuous flow is shown. Figure 2.1B Shown are gel permeation chromatography curves for batch and flow photoinitiator polymerizations of DMA, where [DMA]:[photoinitiator] = 10,000:1 (5 M monomer concentration, 1 h irradiation). Figure 2.1C Pseudo-first order kinetic rate plots for batch and flow polymerizations are shown. Flow polymerizations exhibit an enhanced apparent propagation rate constant (k p,app ).
[0026] Figure 2.2A -B shows the reverse miniemulsion photoinitiator polymerization of N,N-dimethylacrylamide (DMA) in a continuous flow, where Figure 2.2A shows linear pseudo-first-order kinetics, Figure 2.2B The number average molecular weight (M) at full conversion is shown. n ) and DMA (PI 1 targeting M n =1,000,000 g / mol) of continuous flow inverse miniemulsion photoinitiator polymerization conversion. The linearity in the kinetics, the increase in molecular weight with increasing conversion, and the relatively low The value indicates that the polymerization reaction is controlled.
[0027] Figure 2.3A -B shows the dynamic light scattering results, where Figure 2.3A Particle sizes before and after incubation (1 h) in various batch and flow reactors without UV irradiation are shown; Figure 2.3B Particle sizes before polymerization and samples collected after two and four retention times (1 h) are shown. The final polymer particles were comparable in size.
[0028] Figure 2.4 The GPC (gel permeation chromatography) curves of PDMA and PDMA-b-PDMA mediated by PI 2 are shown. PDMA was prepared under reverse phase miniemulsion conditions and chain extended with DMA in a continuous flow to obtain PDMA-b-PDMA. The void volume of the GPC system was 10 mL. DETAILED DESCRIPTION
[0029] definition
[0030] For convenience, before further describing the present invention, certain terms used in the specification, examples and appended claims are collected here. It should be understood that the present disclosure is not limited to the specific embodiments described, and therefore can certainly vary. It should also be understood that the terms used here are only for the purpose of describing specific embodiments, and not for limitation, because the scope of the present disclosure will be limited only by the appended claims. These definitions should be read in light of the remainder of the present disclosure and understood by those skilled in the art. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those of ordinary skill in the art are generally understood. Unless otherwise limited in specific circumstances, the terms used in this specification are defined as follows.
[0031] Where a range of values is provided, it is understood that every intervening value between the upper and lower limits of the range, to one-tenth of the unit of the lower limit (unless the context clearly indicates otherwise), and any other specified value or intervening value within the stated range, is encompassed within the disclosure. The upper and lower limits of these smaller ranges may independently be included in the smaller ranges, and are also included within the disclosure, subject to any specifically excluded limits within the stated range. Where the stated range includes one or both limits, ranges excluding one or both of the included limits are also included within the disclosure.
[0032] It will be apparent to those skilled in the art, after reading this disclosure, that each of the various embodiments described and illustrated herein has discrete components and features that can be easily separated or combined with the features of any of the other several embodiments without departing from the scope or spirit of the disclosure. Any enumerated method can be performed in the order of the enumerated events or in any other order that is logically possible.
[0033]
[00136] Embodiments of the present disclosure will employ, unless otherwise indicated, techniques of chemistry, biochemistry, molecular biology, genetics, and the like, which are within the skill of the art. Such techniques are fully explained in the literature.
[0034] The following examples are presented to provide those of ordinary skill in the art with a complete disclosure and description of how to implement the present methods and use the compositions and compounds disclosed and claimed herein. Efforts have been made to ensure the accuracy of the numbers (such as amounts, temperatures, etc.), but some errors and deviations should be considered. Unless otherwise indicated, parts are by weight, temperatures are in ° C, and pressures are equal to or close to atmospheric pressure. Standard temperature and pressure are defined as 20 ° C and 1 atmosphere.
[0035] Before describing the embodiments of the present disclosure in detail, it should be understood that, unless otherwise stated, the present disclosure is not limited to specific materials, reagents, reaction materials, manufacturing processes, etc., as they may vary. It should also be understood that the terms used herein are only for the purpose of describing specific embodiments and are not intended to be limiting. In the present disclosure, steps may also be performed in different orders, which is logically possible.
[0036] The articles "a," "an," and "the" are used to refer to one or more (ie, to at least one) of the grammatical objects of the article.
[0037] As used herein, "about," "approximately," and the like, when used in conjunction with a numerical variable, generally refers to the value of that variable and all values of that variable that are within experimental error (e.g., within a 95% confidence interval about the mean) or within + / - 10% of the indicated value, whichever is greater.
[0038] The terms "comprising", "including", "containing", "characterized by" and their grammatical equivalents are used in an inclusive, open sense, meaning that additional elements may be included. It should not be interpreted as "consisting only of..."
[0039] As used herein, "subject" refers to any living entity composed of at least one cell. Living organisms can be as simple as, for example, a single isolated eukaryotic cell or a cultured cell or cell line, or as complex as mammals, including humans, and animals (e.g., vertebrates, amphibians, fish, mammals such as cats, dogs, horses, pigs, cows, sheep, rodents, rabbits, squirrels, bears, primates (e.g., chimpanzees, gorillas, and humans)).
[0040] As used herein, the terms "treating" and "treatment" may generally refer to obtaining a desired pharmacological and / or physiological effect. In terms of preventing or partially preventing a disease, symptom, or disorder, the effect may be, but need not necessarily be, prophylactic. The effect may be therapeutic, i.e., partially or completely curing a disease, condition, or symptom, or attributing to an adverse effect of the disease, disorder, or condition. The term "treatment" as used herein may include any one or more of the following: (a) preventing a disease from occurring in a subject who may be susceptible to the disease but has not yet been diagnosed with the disease; (b) inhibiting the disease, i.e., preventing its development; and (c) alleviating the disease, i.e., alleviating or ameliorating the disease and / or its symptom or condition. The term "treatment" as used herein may refer to a single therapeutic treatment, a single prophylactic treatment, or both therapeutic and prophylactic treatments. A person in need of treatment (a subject in need of treatment) may include a person who already has the disorder and / or a person in need of prevention of the disorder. As used herein, the term "treating" may include inhibiting a disease, disorder, or condition, such as inhibiting its progression; as well as alleviating the disease, disorder, or condition, such as causing regression of the disease, disorder, and / or condition. Treating the disease, disorder, or condition may include ameliorating at least one symptom of the particular disease, disorder, or condition, even if the underlying pathophysiology is not affected, such as treating pain in a subject by administering an analgesic, even if the agent does not treat the cause of the pain.
[0041] As used herein, "preventative" and "prevention" refer to hindering or preventing a disease or condition before it occurs, even if it has not been diagnosed, or while the disease or condition is still in a subclinical stage.
[0042] "Polymer" is understood to include, but is not limited to, homopolymers, copolymers, such as block, graft, random and alternating copolymers, terpolymers, etc., and blends and modifications thereof.
[0043] As used herein, the term "disease" refers to an interruption, cessation or disorder of a body function, system or organ.
[0044] As used herein, "derivative" refers to a compound or molecule prepared from a parent compound by one or more chemical reactions.
[0045] discuss
[0046] The present disclosure provides compositions comprising at least one water-soluble polymer having a molecular weight of about 10 kDa to 10,000 kDa, methods for preparing the water-soluble polymers, structures having the water-soluble polymers, and methods of using the same. The present disclosure provides branched and hyperbranched water-soluble polymers and methods for preparing branched and hyperbranched water-soluble polymers.
[0047] On the one hand, the present disclosure provides methods for synthesizing one or more types of water-soluble polymers, such as those provided herein. The molecular weight of the prepared water-soluble polymer can be about 10kDa to 10,000kDa. These methods can be prepared by multiphase inverse miniemulsion systems, emulsion preparation and dispersion methods, and polymerization methods under intermittent and flow reactor conditions. Provided herein and / or the chemical properties of the emulsion continuous phase, dispersed phase, surfactant, stabilizer, monomer, initiator structure and the resulting water-soluble polymer can be determined.
[0048] In one aspect, the multiphase inverse miniemulsion process has one or more of the following characteristics: (1) the ability to prepare high molecular weight water-compatible polymers in low viscosity, high solids form; (2) forming a water-in-oil emulsion of an aqueous solution of vinyl monomers in an inert hydrocarbon liquid organic dispersion medium; (3) forming droplets having a particle size in the range of 50-500 nanometers; and (4) free radical polymerization of the monomers in the dispersion medium to form polymer droplets.
[0049] The present disclosure provides water-soluble polymers with high molecular weight, and the use of the water-soluble polymers for gelation and restoration of functional biological properties of mucin networks and surfaces. Embodiments of water-soluble polymers can have one or more of the following characteristics: (1) mucoadhesion: the ability to form covalent or non-covalent interactions with naturally occurring mucins (e.g., non-covalent interactions can be described as supramolecular interactions, including but not limited to hydrogen bonds, ionic bonds, van der Waals interactions, hydrophobic interactions, and macromolecular chain entanglements); (2) viscoelasticity (mucolability): the interactions between water-soluble polymers and mucins should generally be reversible, such that these interactions are reversed by mechanical forces, background hydrolysis, redox reactions, or exchanges with other interactions; and (3) mucin integration: due to the ability of water-soluble polymers to form interactions with natural mucins and due to their similar hydrophilicity to natural mucins, they are able to integrate into mucin networks and / or interact with membrane-bound mucins. The combination of these three properties enables the materials described in the present invention to enhance the hydration and rheology of mucinized surfaces in vivo. The water-soluble polymers of the present disclosure are designed to interact weakly with mucins, either through a rapidly reversible interaction, or by forming only minimal interactions with mucins.
[0050] The water-soluble polymers disclosed herein can be synthesized by polymerization of hydrophilic monomers to obtain highly water-soluble polymers. In one aspect, the water-soluble polymers can have a total molecular weight of about 10 kDa to 10,000 kDa or about 100 kDa to 10,000 kDa. Most (e.g., greater than 50% or about 75 to 99.9% by weight) molecular weights of these polymers come from inert hydrophilic functional groups (e.g., N, N-dimethylacrylamide) in the main chain. The functionality and / or structure (e.g., linear or nonlinear) of the monomers and / or the functional groups on the monomers can be selected based on the ability to restore the shear-thinning behavior of the mucin gel by forming weak, transient, reversible interactions with mucin and each other. These transient interactions can be covalent (e.g., borate formation, disulfide formation) or non-covalent (e.g., hydrogen bonding, calcium bridging by carboxylates). In other words, a portion of the units of the polymer are mucin binding units. In one example, these interactions can be achieved by polymers composed of N,N-dimethylacrylamide, acrylic acid, 3-(acrylamide)phenylboronic acid and pyridyl disulfide acrylamide, respectively. In addition, the water-soluble polymers of the present disclosure can also be composed of a mixture of hydrophobic and hydrophilic monomers (e.g., by polymerization of acrylates or styrene and maleimide), provided that the total polymer is water-soluble. In one aspect, the functionality responsible for transient interactions with mucin or the water-soluble polymers of the present disclosure (e.g., mucin binding units, such as monomers and / or functional groups) is typically sparsely distributed throughout the backbone to constitute 0.1% to 25% of the total molecular weight of the water-soluble polymer. In one aspect, low levels of monomers / functional groups can be isolated in specific regions of the polymer, where the binding functionality is present along the polymer backbone in a gradient-type manner, or isolated to regions primarily at one or both ends of the polymer (e.g., terminal positioning) or only in the middle region of the polymer (e.g., central positioning). Thus, the weight percentage of the mucin binding unit can range from very low (eg, 0.1 to 1 weight %) to any percentage within the range of 0.1 to 25 weight % of the total molecular weight of the water-soluble polymer.
[0051] The term "water-soluble" in "water-soluble polymer" refers to any polymer that is soluble in water at room temperature. Typically, a solution of a water-soluble polymer will transmit at least about 75%, more preferably at least about 95% of the light transmitted after filtering the same solution. By weight, the water-soluble polymer is preferably at least about 35% (by weight) soluble in water, more preferably at least about 50% (by weight) soluble in water, still more preferably about 70% (by weight) soluble in water, and even more preferably about 85% (by weight) soluble in water. Most preferably, the water-soluble polymer is about 95% (by weight) soluble in water or completely soluble in water.
[0052] In one aspect, the present disclosure provides an ophthalmic solution comprising a water-soluble polymer. In one aspect, the present disclosure provides a method of treating or preventing a condition in a subject's eye, the method comprising applying to the eye an effective therapeutic amount of an ophthalmic solution disclosed herein, whereby the water-soluble polymer forms a non-covalent interaction or a reversible covalent bond with a mucin or a mucin-binding protein. In another aspect, the water-soluble polymer can form a layer on a structure or device, wherein the device is used in a mucin environment.
[0053] In one aspect, the composition includes a water-soluble polymer (e.g., linear or nonlinear) having a molecular weight of about 100 kDa to 10,000 kDa. In one aspect, the composition can include other types of water-soluble polymers. It should be noted that in most discussions herein, reference is made to a "first water-soluble polymer," but in compositions comprising two or more types of water-soluble polymers, the description of "first water-soluble polymer" provided herein is equally applicable to other types of water-soluble polymers, wherein the two types of water-soluble polymers are chemically different.
[0054] The first water-soluble polymer includes a plurality of main chain units (e.g., linear or non-linear) and at least one first type of mucin binding unit. Based on molecular weight, the main chain unit accounts for greater than 50% or about 75% to 99.9% of the first water-soluble polymer. Based on molecular weight, the first type of mucin binding unit accounts for up to 50% or about 0.1% to 25% of 1 unit of the first water-soluble polymer. In other aspects, the first water-soluble polymer may include a second type or a third type of mucin binding unit. Based on molecular weight, each type of mucin binding unit can account for up to 25% of 1 unit of the first water-soluble polymer, 1 functional unit to about 5%, about 0.1 to 25%, about 0.1 to 20%, about 0.1 to 15%, about 0.1 to 10%, about 0.1 to 5%, or about 0.1 to 1%.
[0055] In one embodiment, the first water-soluble polymer can be linear or non-linear, such as star-shaped, branched, hyperbranched, comb-shaped / brush-shaped, graphic copolymer, bottle brush-shaped, or cyclic. In one aspect, the first water-soluble polymer can be a first branched water-soluble polymer or a hyperbranched first water-soluble polymer. In one embodiment, the first water-soluble polymer can be a polyelectrolyte, a polyampholyte, or a polyzwitterion.
[0056] A linear polymer can be defined as a macromolecular structure composed of monomer units covalently linked together in a sequential and unidirectional manner to form a single continuous chain. This architecture lacks crosslinks, side chains, and network structures that are created by the connections between polymer chains.
[0057] Branched polymers can be defined as macromolecular frameworks in which one or more side chains extend from the main linear backbone. Such frameworks can be generated, for example, by the introduction of monomers with multiple reactive sites during polymerization. These side chains of varying length, regularity and density form a more complex heterogeneous topology than linear polymers. The degree of branching (DB) can be calculated using the following formula:
[0058]
[0059] Where D represents the molar equivalents of dendritic or branched units and L represents the molar equivalents of linear units. Branched polymers may be defined herein as having a DB greater than 0 but less than 0.4.
[0060] Hyperbranched polymers can be defined as a macromolecular structure with a tree-like topology, which distinguishes it from conventional branched polymers. The distinguishing feature of hyperbranched polymers is their high DB, greater than 0.4 but less than 1.
[0061] In one aspect, the backbone units may include monomer units and copolymers including monomer units. In one aspect, the first water-soluble polymer may be a block copolymer, a random copolymer, a statistical copolymer, an alternating copolymer, or a gradient copolymer. In one aspect, the first water-soluble polymer is a block copolymer, such as an AB diblock copolymer or an ABA triblock copolymer. Optionally, the mucin binding unit is isolated on the A block of the AB diblock copolymer or the A block of the ABA triblock copolymer. In one aspect, the A and B blocks of the AB or ABA block copolymer contain a mixture of comonomer units. In one aspect, the comonomer units in the A or B blocks may be arranged in an alternating, random, statistical or gradient manner. On the other hand, one or more blocks of the copolymer may be water-insoluble as long as the entire copolymer is water-soluble. For example, one of the A block or B block in the AB diblock copolymer or the ABA triblock copolymer may be water-insoluble, wherein the copolymer itself is water-soluble.
[0062] Gradient copolymers are polymers with more than one monomer unit, where the frequency of occurrence of at least one monomer unit changes gradually along the polymer chain. Statistical copolymers are copolymers where the sequential distribution of monomer units follows a known statistical law and is based on relative reactivity.
[0063] In one aspect, the monomer units can be selected from: acrylamide monomers, methacrylamide monomers, acrylate monomers, methacrylate monomers, styrene monomers, vinyl pyridine monomers, maleimide monomers, maleic anhydride derived monomers, vinyl ester monomers, vinyl amide monomers, vinyl halide monomers, or derivatives of any of these monomers. In a specific aspect, the backbone unit may include a monomer unit or a copolymer including a monomer unit, wherein the monomer unit is selected from: acrylamide, N,N-dimethylacrylamide, N,N-dialkylacrylamide, N-alkylacrylamide, N,N-dialkylmethacrylamide, N-alkylmethacrylamide, alkylmethacrylate, alkylacrylate, oligo(ethylene glycol)acrylate, oligo(ethylene glycol)methacrylate, oligo(ethylene glycol)acrylamide, oligo(ethylene glycol)methacrylamide, substituted propylene In one aspect, the backbone unit is N,N-dimethylacrylamide. In another aspect, the backbone unit is N-hydroxyethylacrylamide (n is 1 to 10) with the following structure.
[0064]
[0065] Each type (e.g., first type, second type, third type) of mucin binding unit can be functionalized so that the water-soluble polymer has a property of changing the hydration, rheology, or both of the mucin-based polymer, the second water-soluble polymer, or a combination thereof. Changing the properties of hydration, rheology, or both can be achieved by mucoadhesion, mucoadhesion plasticity, mucoadhesion integration, or a combination thereof as described herein.
[0066] In one aspect, the mucin binding unit may include a monomer unit or a copolymer including a monomer unit, wherein the monomer unit includes a functional group, such as a boronic acid group, a carboxylate group, a carboxylic acid group, a hydrogen bonding group, a hydrophobic group, or a group capable of forming a disulfide bond. In one embodiment, the plurality of functional groups are distributed in a uniform, random, gradient, or blocky order in the first water-soluble polymer, and in a specific aspect, are distributed at the end of the water-soluble polymer.
[0067] Each type of mucin binding unit can be a monomer unit or a copolymer fragment comprising the monomer unit. The monomer unit can be selected from: acrylic acid, methacrylic acid, 4-vinylbenzoic acid, 4-(acrylamide)phenylboronic acid, 3-(acrylamide)phenylboronic acid, 2-(acrylamide)phenylboronic acid, 4-vinylphenylboronic acid, 3-vinylphenylboronic acid, 2-vinylphenylboronic acid, 2(4-((2-acrylamideethyl)carbamoyl)-3-chlorophenyl)boric acid, (4-((2-acrylamideethyl)carbamoyl)-3-fluorophenyl)boric acid, (4-((2-acrylamideethyl)carbamoyl)-3-bromophenyl)boric acid, (4-((2-acrylamideethyl)carbamoyl)-3-bromophenyl)boric acid,
[0063] The following are examples of the present invention: (i) ethyl (( ...
[0068]
[0069] In one aspect, the first water-soluble polymer can have a chemical structure such as: In one aspect, unit a is a backbone unit, and m is greater than 50% or about 75% to 99.9% of the first water-soluble polymer based on molecular weight. In one aspect, m and n, independently of each other, can be from about 1000 to 100,000. Unit b is a first type of mucin binding unit, and n is from 1 unit to 50% or about 0.1% to 25% of the first water-soluble polymer based on molecular weight (or another range provided herein). Unit a and unit b are different from each other. R a4 and R b4 The dashed lines indicate that X and Y are optionally present, respectively.
[0070] In one aspect, R a1 , R a2 , R a3 , R a4 , R b1 , R b2 , R b3 and R b4 Independently of each other, they can be H, -OR1, -NR1R2, -N + (R1)3, -N + (R1)2(R2), -N +(R1)(R2)(R3), -S(O)2R1, -S(O)2OR1, -S(O)2NR1R2, -NR1S(O)2R2, -NR1C(O)R2, -C(O)R1, -C(O)OR1, -C(O)NR1R2, -NR1C(O)OR2, -NR1C(O)NR1R2, -OC(O)NR1R2, -NR1S(O)2NR1R2, -C(O)NR1S(O)2NR1R2, catechol, boronic acid group and pyridyl disulfide group, wherein each R1, R2 and R3 are independently H or linear or branched C 1-18 Alkyl, and -C(O)OCH2CH2-OH, -C(O)OCH2CH2-N(CH3)2, -C(O)OCH2CH2-N + (CH3)3, -C(O)OCH2CH2-OSO3 – , -C(O)OCH2CH2-OSO3H, -C(O)OCH2CH2-SO3 – , -C(O)OCH2CH2-SO3H, and -C(O)N(H)C((CH3)2)CH2SO3 – , -C(O)N(H)C((CH3)2)CH2SO3H.
[0071] In one aspect, X can be N or C and Y can be C or N. In a specific aspect, X and Y are C.
[0072] In another aspect, the first water-soluble polymer has, for example: Chemical structure of. In one aspect, unit a can be a backbone unit and m is greater than 50% or about 75% to 99.9% of the first polymer based on molecular weight. In one aspect, m, n and o can be about 1000 to 100,000, independently of each other. Unit b can be a first type of mucin binding unit and n is 1 unit to 50% or about 0.1 to 24% (or another range provided herein) of the first polymer based on molecular weight. Unit c is a second type of mucin binding unit and o is 1 unit to 50% or about 0.1 to 24% (or another range provided herein) of the first polymer based on molecular weight. Unit a and unit b are different from each other, or unit a, unit b and unit c are different from each other. R a4 , R b4 and R c4 The dashed lines indicate optional presence based on X, Y and Z, respectively. In one aspect, for example, unit c may be responsible for mucin binding or may be responsible for further enhancing the hydrophilicity of the backbone (eg, by introducing charges).
[0073] In one aspect, R a1 , R a2 , Ra3 , R a4 , R b1 , R b2 , R b3 , R b4 , R c1 , R c2 , R c3 and R c4 Independently of each other, they can be H, -OR1, -NR1R2, -N + (R1)3, -N + (R1)2(R2), -N + (R1)(R2)(R3), -S(O)2R1, -S(O)2OR1, -S(O)2NR1R2, -NR1S(O)2R2, -NR1C(O)R2, -C(O)R1, -C(O)OR1, -C(O)NR1R2, -NR1C(O)OR2, -NR1C(O)NR1R2, -OC(O)NR1R2, -NR1S(O)2NR1R2, -C(O)NR1S(O)2NR1R2, catechol, boronic acid group and pyridyl disulfide group, wherein each R1, R2 and R3 are independently H or linear or branched C 1-18 Alkyl, and -C(O)OCH2CH2-OH, -C(O)OCH2CH2-N(CH3)2, -C(O)OCH2CH2-N + (CH3)3, -C(O)OCH2CH2-OSO3 – , -C(O)OCH2CH2-OSO3H, -C(O)OCH2CH2-SO3 – , -C(O)OCH2CH2-SO3H, and -C(O)N(H)C((CH3)2)CH2SO3 – , -C(O)N(H)C((CH3)2)CH2SO3H.
[0074] In one aspect, X can be N or C, wherein Y can be C or N, wherein Z can be N or C. In a specific aspect, X, Y and Z are C.
[0075] In another aspect, the first water-soluble polymer has a polymer having, for example: Chemical structure of. In one aspect, unit a can be a backbone unit and m is greater than 50% or about 75% to 99.9% of the first water-soluble polymer based on molecular weight. In one aspect, m, n and o can be about 1000 to 100,000, independently of each other. Unit b can be a first type of mucin binding unit and n is 1 unit to 50% or about 0.1 to 24% of the first polymer based on molecular weight. Unit c can be a second type of mucin binding unit and o is about 0.1 to 24% of the first water-soluble polymer based on molecular weight. Unit d can be a third type of mucin binding unit and o is 1 unit to 50% or about 0.1 to 24% of the first water-soluble polymer based on molecular weight. Unit a and unit b can be different from each other, unit a, unit b and unit c can be different from each other, or unit a, unit b, unit c and unit d can be different from each other. R a4 , R b4 , R c4 and R d4 The dashed lines indicate optional presence based on X, Y, Z and Q, respectively. In one aspect, for example, unit c and / or unit d may be responsible for mucin binding or may be responsible for further enhancing the hydrophilicity of the backbone (eg, by introducing charges).
[0076] In one aspect, R a1 , R a2 , R a3 , R a4 , R b1 , R b2 , R b3 , R b4 , R c1 , R c2 , R c3 , R c4 , R d1 , R d2 , R d3 and R d4 Independently of each other, they can be H, -OR1, -NR1R2, -N + (R1)3, -N + (R1)2(R2), -N + (R1)(R2)(R3), -S(O)2R1, -S(O)2OR1, -S(O)2NR1R2, -NR1S(O)2R2, -NR1C(O)R2, -C(O)R1, -C(O)OR1, -C(O)NR1R2, -NR1C(O)OR2, -NR1C(O)NR1R2, -OC(O)NR1R2, -NR1S(O)2NR1R2, -C(O)NR1S(O)2NR1R2, catechol, boronic acid group and pyridyl disulfide group, wherein each R1, R2 and R3 are independently H or linear or branched C1-18 Alkyl, and -C(O)OCH2CH2-OH, -C(O)OCH2CH2-N(CH3)2, -C(O)OCH2CH2-N + (CH3)3, -C(O)OCH2CH2-OSO3 – , -C(O)OCH2CH2-OSO3H, -C(O)OCH2CH2-SO3 – , -C(O)OCH2CH2-SO3H, and -C(O)N(H)C((CH3)2)CH2SO3 – , -C(O)N(H)C((CH3)2)CH2SO3H.
[0077] In one aspect, X can be N or C, wherein Y can be C or N, wherein Z can be N or C, wherein Q can be N or C. In a specific aspect, X, Y, Z and Q are C.
[0078] In one aspect, the water-soluble polymers disclosed herein can be prepared by aqueous reversible deactivation free radical polymerization (see, Chem, 2017, 2(1), 93-101). In one embodiment, the polymer material is prepared by xanthate (MADIX) polymerization exchange design of macromolecules. In one embodiment, the polymer material is prepared by photoinitiator polymerization. These molecular weight controllable materials can also be obtained by other controlled free radical polymerization methods, such as atom transfer radical polymerization and nitroxide-mediated polymerization. In addition, these materials can be obtained by conventional free radical, anionic, cationic, ring-opening and ring-opening metathesis polymerization.
[0079] In particular, the present disclosure provides a method for preparing a first water-soluble polymer provided herein by polymerizing a backbone unit (e.g., linear or nonlinear) and at least one mucin binding unit to form a first water-soluble polymer. The polymerization can be free radical polymerization, conventional free radical polymerization, reversible deactivation free radical polymerization, reversible addition-fragmentation chain transfer (RAFT) polymerization, macromolecular design of xanthate exchange (MADIX) polymerization, photoinitiator polymerization, atom transfer radical polymerization (ATRP) or stable free radical polymerization (SFRP).
[0080] A typical photoinitiator polymerization initiated by trithiocarbonate is as follows. n ≥5.00×10 6 g / mol). In a 10 mL Schlenk flask, DMA (394 mg, 3.97 mmol) and trithiocarbonate iniferter (20.0 μg, 7.45×10 -5mmol, from a 1.00 mg / mL dimethyl sulfoxide (DMSO) stock solution) was dissolved in water (1.70 mL, 2M [DMA]), and N,N-dimethylformamide (DMF) (0.100 mL) was added as an internal standard. The iniferter stock solution was stored between 2 and 6 °C for further use. Argon was bubbled through the polymerization solution for 20 minutes. The reaction vessel was placed 2.50 cm from an ultraviolet (UV) light source with an intensity of 7.0 mW / cm 2 , and initiates polymerization upon irradiation. 1 Monomer conversion was determined by HNMR spectroscopy, monitoring the disappearance of the DMA vinyl peak (d, 1H, 5.60 ppm) relative to DMF (s, 1H, 8.02 ppm). Prior to molecular weight characterization, each reaction aliquot was dried by lyophilization and dissolved in SEC solvent (1 mg / mL) for at least 24 hours.
[0081] An example of chain extension polymerization demonstrating the ability to prepare high molecular weight block copolymers by photoinitiator polymerization is as follows. DMA (417 mg, 4.20 mmol) and trithiocarbonate iniferter (0.100 mg, 3.72×10 -4 mmol, from a 1.00 mg / mL DMSO stock solution) was dissolved in water (3.70 mL 1M [DMA]), and DMF (0.100 mL) was added as an internal standard. Argon was bubbled through the polymerization solution for 20 minutes. The reaction vessel was placed 2.50 cm from a UV light source with an intensity of 7.0 mW / cm 2 , and initiate polymerization during irradiation. After irradiation for 24 hours, a small amount of solvent is removed and the 1 Monomer conversion was determined by monitoring the disappearance of the vinyl DMA peak (d, 1H, 5.60 ppm) relative to DMF (s, 1H, 8.02 ppm) by HNMR spectroscopy, and molecular weight was characterized by SEC. Polymerization of the first block of poly(DMA) (PDMA) achieved >95% monomer conversion. DMA (420 mg, 4.24 mmol) was dissolved in water (3.10 mL), DMF (0.100 mL) and the previous PDMA polymerization mixture. Argon was passed through the viscous solution for 20 min and chain extension was initiated upon irradiation.
[0082] In one aspect, high molecular weight (e.g., about 1,000,000 or according to the molecular weight described herein) water-soluble polymers prepared by reverse phase (water-in-oil) reproducible photoinitiator polymerization. Monomers such as DMA, NVP and other water-soluble monomers (including all monomers described herein) are very suitable for these types of processes. One goal is to prepare highly wettable surfaces on contacts and in ophthalmic preparations such as described herein. Intermittent and continuous flow systems are described herein and in the Examples.
[0083] Now that various aspects have been described, additional details about the preparation methods are provided. On the one hand, the present disclosure includes the synthesis of ultrahigh molecular weight water-soluble polymers by photoinitiator polymerization under reverse phase miniemulsion conditions. The method can be a catalyst-free multiphase process, which is mediated by low-intensity ultraviolet irradiation and provides rapid polymerization rates, excellent molecular weight control, high polymer end group fidelity, time control, advanced architecture and most significantly viscosity control. As described herein and in the examples, polymerization conditions are improved based on the type of surfactant, co-stabilizer and iniferter to obtain acrylamide-based homopolymers and block copolymers with molecular weights exceeding 1,000,000Da at ambient temperature. This method of well-defined ultrahigh molecular weight polymers can overcome one or more problems caused by high viscosity to facilitate final scale-up. The process can be carried out under, for example, intermittent or continuous flow conditions. The method using the multi-phase reverse miniemulsion process has at least one of the following characteristics: (1) the ability to prepare high molecular weight water-compatible polymers in a low viscosity, high solids form; (2) forming an oil-in-water emulsion of an aqueous solution of vinyl monomers in an inert hydrocarbon liquid organic dispersion medium; (3) forming droplets with a particle size in the range of 50-500 nm; and (4) free radical polymerization of the monomers in the dispersion medium to form polymer droplets.
[0084] In a specific embodiment, the first water-soluble polymer can be non-linear, such as a branched or hyperbranched hydrocarbon. The polymerization can be free radical polymerization, conventional free radical polymerization, self-condensation vinyl polymerization (SCVP), reversible deactivation radical polymerization, reversible addition-fragmentation chain transfer (RAFT) polymerization, macromolecular design of xanthate exchange (MADIX) polymerization, iniferter polymerization, atom transfer radical polymerization (ATRP) or stable free radical polymerization (SFRP).
[0085] To obtain branched structures, monofunctional (i.e., containing one vinyl group or functional group capable of linear polymerization) water-soluble (e.g., N,N-dimethylacrylamide (DMA), N-hydroxyethylacrylamide (HEAm), 2-methacryloyloxyethylphosphorylcholine (MPC), acrylic acid (AA), etc.), monomers or any mixture of water-soluble monomers can be combined with polyfunctional (i.e., containing two or more vinyl groups or other functional groups capable of free radical polymerization) water-soluble monomers (e.g., N,N'-methylenebisacrylamide, polyethylene glycol dimethacrylate, polyethylene glycol diacrylate, polyethylene glycol diacrylamide, N-[tris-(3-acrylamidopropoxymethyl)-methyl]acrylamide, etc. In this context, vinyl is defined as a group derived from the functional group H2C=CHR and which, when polymerized, produces an extended alkane chain (-CH2-CHR) n .
[0086] The molecular weight of the branched and hyperbranched polymers obtained by these methods can range from 10 kDa to 10,000 kDa. In order to achieve these molecular weights without macroscopic gelation, the multifunctional monomers must be added in a low mole % ratio relative to the monofunctional monomers (<1% relative to the monofunctional monomers). The degree of branching of the polymers prepared by this method is greater than 0, but less than 0.4.
[0087] The figure below illustrates the formation of branched polymers.
[0088]
[0089] The branched polymer was prepared as follows: 1000 mL reaction volume polymerization was carried out in DMSO / water 15 / 85 w / w% with a solid content of 5%. After the monofunctional monomer was added to DMSO, water was added and stirred until it was completely dissolved. The solution was transferred to a reactor, where the multifunctional monomer and free radical initiator were added in sequence. The solution was purged with nitrogen at a flow rate of 150 mL / min for 25 minutes, and then purged at a flow rate of 40 mL / min to maintain a nitrogen atmosphere. A typical reaction uses less than or equal to 0.15 mol% of the multifunctional monomer and 0.25 mol% of the free radical initiator relative to the monofunctional monomer. The temperature schedule of the typical reaction is as follows: 16-56°C heating curve, 2 hours; 56°C hold, 10 hours; 56-16°C cooling curve, 2 hours.
[0090] In another embodiment, self-condensing vinyl polymerization (SCVP) can be used to synthesize hyperbranched polymers by polymerization of initiating monomers (i.e., molecules containing vinyl groups and groups capable of initiating polymerization or capable of being converted to groups capable of initiating polymerization, such as thiocarbonylthio groups for RAFT polymerization or halogens for ATRP). The polymerization proceeds through the reaction of the vinyl groups, and the resulting oligomers are linked together in a step-growth manner by pendant reactions on the initiating monomer center to form a highly branched structure. In this context, vinyl groups are defined as groups derived from the functional group H2C=CHR and, when polymerized, produce extended alkane chains (-CH2-CHR) n In the following reactions, X can be 1-20 carbons, 1-10 carbons, or 1-6 carbons (e.g., linear, branched, cyclic, aromatic, and combinations thereof), and includes an appropriate amount of hydrogen (e.g., -CH2-, (-CH2) n=1-20或1-10,或1-6或-CH3 ).
[0091]
[0092] We have not yet synthesized these polymers via SCVP, but we chose to include it because it is a very common synthetic route to this polymer architecture.
[0093] The molecular weight of branched or hyperbranched polymers obtained by these methods ranges from 10 kDa to 10,000 kDa. The degree of branching (DB) of polymers synthesized by SCVP is greater than 0.4 but less than 1. Polymers with a DB of 0.01 to 0.4 are called block hyperbranched polymers and can also be synthesized by SCVP or other polymerization methods.
[0094] monomer:
[0095] In one aspect, the monomer units can be one or more of the following: acrylamide monomers, methacrylamide monomers, acrylate monomers, methacrylate monomers, styrenic monomers, vinyl pyridine monomers, maleimide monomers, maleic anhydride derived monomers, vinyl ester monomers, vinyl amide monomers, vinyl halide monomers, substituted acrylamides, substituted methacrylamides, or derivatives of any of these monomers. In a specific aspect, the backbone unit may include a monomer unit or a copolymer including a monomer unit, wherein the monomer unit is selected from: acrylamide, N,N-dimethylacrylamide, N,N-dialkylacrylamide, N-alkylacrylamide, N,N-dialkylmethacrylamide, N-alkylmethacrylamide, alkyl methacrylate, alkyl acrylate, oligo(ethylene glycol)acrylate, oligo(ethylene glycol)methacrylate, oligo(ethylene glycol)acrylamide, or one or more of oligo(ethylene glycol)methacrylamide, other substituted acrylates (e.g., substitution (R) includes functional groups such as hydroxyl, amine, carboxyl, sulfonic acid, etc.), other substituted methacrylates (e.g., substitution (R) includes functional groups such as hydroxyl, amine, carboxyl, sulfonic acid, etc.). In a specific aspect, the backbone unit is N,N-dimethylacrylamide.
[0096] In another aspect, the backbone unit is N-hydroxyethyl acrylamide (n is 1 to 10) having the following structure.
[0097]
[0098] Photoinitiator / Initiator / Wavelength / Intensity:
[0099] In one aspect, photoinitiator polymerization can be used to synthesize high molecular weight polymers by the inverse miniemulsion method. An example of a photoinitiator is a photoinitiator, a chain transfer agent, and a chain terminator having the following chemical formula:
[0100]
[0101] wherein R1 is a divalent alkyl group of 1 to 12 carbon atoms, R2 and R3 are each independently H or an alkyl group of 1 to 12 carbon atoms, and R4 is -H, -OH or -COOH; wherein X represents -S, -O or -NH; and wherein Y represents a functional group capable of activating free radical addition of a trans-vinyl monomer. In one aspect, a plurality of photoinitiators can be chemically linked together via any one of R2, R3, R4 and / or Y.
[0102] In photoinitiator polymerization, the irradiation step initiates photopolymerization. The irradiation wavelength commensurate with the photoinitiator used can be determined by one of ordinary skill in the art based on the chemicals used and the desired results. For example, the wavelength can be in the visible spectrum or the ultraviolet (UV) spectrum. The choice of wavelength depends on the choice of initiator system, because the initiator system can generate active centers when absorbing the appropriate wavelength (again, the choice of initiator system can depend on the desired illumination wavelength as described above). The irradiation can be temporal or spatial. The irradiation can determine the temporal and spatial generation of active centers. The instantaneous irradiation can determine the time between the start and end of the polymerization reaction. For example, the irradiation can be continuous or intermittent. The irradiation intensity can be adjusted to affect the free radical generation rate.
[0103] In one embodiment, the polymeric material can be prepared by photoinitiator polymerization. These materials with controlled molecular weight can also be obtained by other controlled radical polymerization methods, such as reversible addition-fragmentation chain transfer polymerization, atom transfer radical polymerization and nitroxide-mediated polymerization. In addition, these materials can be obtained by conventional free radical, anionic, cationic, ring-opening and ring-opening metathesis polymerization.
[0104] Intermittent / Flowing:
[0105] Inverse miniemulsion polymerization can be carried out in batch reactors or under continuous flow conditions in tubular reactors.
[0106] A batch reactor refers to a type of container in which a reaction is carried out and no material is added or removed before the reaction is completed. In the context of the present application, any batch reactor can be used so that light can be evenly distributed throughout the reaction solution. Miniemulsion droplets of about 50-500nm can be formed or generated by ultrasonic action before being added to the batch reactor. Before being collected and polymerized in the batch reactor, miniemulsion droplets with a size range of about 50 to 500nm can be formed in a continuous flow by using an online mixing device. The formed miniemulsion is then irradiated with a predetermined wavelength and intensity in the batch reactor to initiate polymerization. The temperature of the batch reactor is typically maintained at about 20°C, but polymerization can be carried out at a temperature of about 7-70°C.
[0107] An embodiment of the inverse miniemulsion polymerization is as follows:
[0108] The general polymerization was carried out as follows: NaCl (60 mg, 1.0 mmol), phosphate buffer (PB, pH = 8, 0.49 mL), DMA (500 mg, 5.0 mmol, 0.52 mL), iniferter 1 (10.6 μL, from 10 mg / mL PB solution, 0.106 mg, 0.000504 mmol), DMF (100 μL), cyclohexane (10 g), and Span 60 (150 mg, 0.35 mmol) were mixed in a 20 mL vial. The DMA concentration in the dispersed phase was 5 M, and the [DMA]:[iniferter] ratio was 10,000:1. The aqueous phase (DMA, PB, DMF, and iniferter) accounted for 9.3 wt% of the entire reaction. The continuous phase was cyclohexane (89 wt%). Span 60 accounted for 1.3% of the total reaction. The added concentration of NaCl was 6 wt% relative to DMA and PB.
[0109] The samples were sonicated for 15 min in a 20 mL vial using an ultrasonic probe (20% amplitude, 15 s on and 5 s off, 1 / 4 inch tip). At this point the samples were transferred to a Schlenk flask (if one was used), or the sample vial was capped with a septum. The samples were degassed using argon for 30 min (10-mL Schlenk) or 40 min (20-mL vial). The light source was turned on to initiate polymerization. A fan cooling device was used and the temperature was maintained at 30°C. The stirring speed used throughout the process was 1,000 rpm. The samples were analyzed using DLS, NMR, and SEC.
[0110] In one aspect, continuous flow or processing in a continuous mode refers to an uninterrupted sequential operation in which polymer product is continuously received. The flow reactor comprises at least: (1) a method for delivering reactants to the reactor, such as a syringe pump or peristaltic pump; (2) an inlet to the reactor; (3) a reaction chamber comprising a length of coiled flow tubing made of glass, fluorinated plastic tubing, or other suitable material having a constant inner diameter; (4) a reaction chamber containing a radiation source capable of initiating polymerization; and / or (5) an outlet at which the reactants leave the tubular reactor and the resulting polymer is collected. In another aspect, multiple flow reactors can be coupled together to synthesize block copolymers by adding monomers in-line after the first reactor. The mixed solution is then irradiated in another reaction chamber to produce the block copolymer.
[0111] In one aspect, by using an in-line mixing device, miniemulsion droplets with a size range of about 50 to 500 nm can be formed in a continuous flow. In another aspect, the miniemulsion droplets can be formed by ultrasonic treatment before being added to the continuous flow reactor. The formed miniemulsion is then passed into a continuous tubular reactor and irradiated at a predetermined wavelength and intensity to initiate polymerization. The temperature of the tubular reactor is typically maintained at about 20°C, but the polymerization can be carried out at a temperature of about 7-70°C.
[0112] One embodiment of a continuous flow reactor design:
[0113] A custom continuous flow reactor was constructed using readily available laboratory materials. The top of a 1L aluminum solvent drum was removed and holes for 1 / 16" OD tubing were drilled in the sides of the drum. The inside of the bottom was lined with a 5m Wave Lighting high energy UV LED (realUV LED) strip. The LED strip output was measured to be 1.0mW / cm 2 . A 6-foot length of 1 / 16" OD 0.03" ID PTFE tubing (Darwin Microfluidics) was wrapped around an aluminum column and placed in the center of the reactor, resulting in a reactor volume of 0.834 mL. A NE-300 syringe pump (New Era Pump Systems Inc.) was used to deliver the polymerization solution, and the syringe was connected to the fluoropolymer tubing using a PEEK 1 / 4-28 flat-bottom connector and a 1 / 4-28 female-to-female Luer lock adapter (IDEX Health & Science). A fan was placed on top of the reactor to maintain ambient temperature.
[0114] An embodiment of a continuous flow reaction:
[0115] The general polymerization was carried out as follows: NaCl (60 mg, 1.0 mmol), phosphate buffer (PB, pH = 8, 0.49 mL), DMA (500 mg, 5.0 mmol, 0.52 mL), iniferter 1 (10.6 μL, from 10 mg / mL PB solution, 0.106 mg, 0.000504 mmol), DMF (100 μL), cyclohexane (10 g) and Span 60 (150 mg, 0.35 mmol) were mixed in a 20 mL vial. The DMA concentration in the dispersed phase was 5 M, and the [DMA]:[iniferter] ratio was 10,000:1. The aqueous phase (DMA, PB and DMF) accounted for 11 wt% of the entire reaction. The continuous phase was cyclohexane (89 wt%). The added concentration of NaCl was 6 wt% relative to DMA and PB.
[0116] The samples were sonicated for 15 min in a 20 mL vial using an ultrasonic probe (20% amplitude, 15 s on and 5 s off, 1 / 4 inch tip). The sample vial was capped with a septum. The sample was degassed with argon for 30 min. The solution was transferred to a 10 mL syringe and placed in a syringe pump. The solution was pumped at 13.9 μL / min for a total retention time of 1 h. Samples were collected as they left the reactor tube and analyzed using DLS, NMR, and SEC.
[0117] Different mixing / dispersion methods:
[0118] There are a variety of methods for preparing miniemulsions. In one aspect, the formation comprises a single step or a series of sequential steps, depending on the nature and process of the starting materials used, and the type of emulsion desired. In general, the methods used to form conventional, nano / mini-emulsions, and even microemulsions can be divided into two categories: high-energy and low-energy methods, also referred to as mechanical and chemical processes, respectively. 1 . High energy methods use mechanical devices such as high pressure homogenizers, microfluidizers, magnetic stirring, mechanical stirring and fixed bed mixers. These mechanical processes generate strong destructive forces that break the dispersed phase into smaller droplets. Low energy methods for forming nano / miniemulsions include phase inversion methods and rely on the spontaneous formation of droplets by exploiting the chemical behavior of the system. Common low energy methods for forming nano / miniemulsions include utilizing phase inversion temperature (PIT) and phase inversion composition (PIC) 2 .
[0119] In one aspect, a method for forming a miniemulsion may include the steps of providing a continuous phase; dispersing a stabilizer (i.e., a surfactant) in the continuous phase; providing a second (dispersed) phase comprising a monomer; and adding the second phase to the first phase in a manner suitable for forming a miniemulsion by a dispersion process, wherein the miniemulsion comprises emulsified particles having an average diameter of less than 1 μm, and wherein the emulsified particles are multilaminar and / or spherical.
[0120] Exemplary High Energy Dispersion Methods:
[0121] Providing mechanical energy input to a two-phase solution to produce emulsion droplets having an average diameter equal to or less than 1 μm, and wherein the emulsified particles are multilayered and / or spherical
[0122] оHigh pressure homogenizer
[0123] оMicrofluidizer
[0124] oHigh shear stirring (magnetic and mechanical)
[0125] оFixed bed mixer
[0126] Exemplary Low Energy Methods
[0127] Controlling the chemical properties (e.g., composition and / or temperature) of the biphasic solution to produce emulsion droplets with an average diameter equal to or below 1 μm, and wherein the emulsified particles are multilaminar and / or spherical
[0128] Phase transition temperature method a
[0129] Phase transformation composition method a
[0130] οBubble rupture at the oil-water interface 3
[0131] οEvaporative ripening 4
[0132] The following content is from "Nano-emulsions: Formation by low-energy methods" 5
[0133] a These methods exploit the chemical energy released by phase transitions occurring during emulsification. Although these phase transitions usually involve a reversal of the surfactant film curvature from positive to negative or vice versa, studies have shown that transitions to structures of surfactant films with zero mean curvature (e.g., bicontinuous microemulsions or lamellar liquid crystal phases) play a key role in the formation of nanoemulsions. Phase transitions are triggered by changes in temperature (phase inversion temperature method, PIT—based on temperature-induced changes in the spontaneous curvature of surfactants) or composition (phase inversion composition method, PIC). The PIT method can only be applied to surfactants that are sensitive to temperature changes, namely polyoxyethylene-type nonionic surfactants, in which temperature changes lead to changes in the hydration of the poly(oxyethylene) chains, resulting in changes in their curvature. In the PIC method, the phase transition is induced by changes in composition during isothermal emulsification, and therefore, it can be applied to surfactants other than the ethoxylated type. 5
[0134] (1)Acosta,E.(2009).Bioavailability of nanoparticles in nutrient and nutraceutical delivery.Current Opinion in Colloid&Interface Science,14(1),3-15
[0135] (2)Wang,Y.(2014).Preparation of Nano-and Microemulsion using PhaseInversion and Emulsion Titration Methods.
[0136] (3)Roché, J. et al., Nanoemulsions obtained via bubble bursting at acompound interface. https: / / arxiv.org / ftp / arxiv / papers / 1312 / 1312.3369.pdf
[0137] (4)Fryd,M.,Mason,T.,The Journal of Physical Chemistry Letters,Time-Dependent Nanoemulsion Droplet Size Reduction By Evaporative Ripening.20101(23),3349-3353.10.1021 / jz101365h https: / / doi.org / 10.1021 / jz101365h
[0138] (5)Solans, C. et al., Nano-emulsions: Formation by low-energymethods.10.1016 / j.cocis.2012.07.003
[0139] Emulsifier:
[0140] Emulsifiers have two main functions: reducing the interfacial tension between phases and forming a barrier between phases. They can control the type of emulsion formed (oil-in-water: O / W, or water-in-oil: W / O). This can be expressed by the hydrophilic-lipophilic balance (HLB) value of the emulsifier. Emulsifiers and / or surfactants with low HLB values will form better W / O emulsions, while emulsifiers and / or surfactants with high HLB values will form better O / W emulsions. In many cases, a combination of emulsifiers / surfactants with high and low HLB values can be combined to produce the best HLB value for the system and most effectively reduce the interfacial tension to produce W / O or O / W droplets. Common emulsifiers include surfactants, which can be divided into ionic and non-ionic types.
[0141]
[0142]
[0143] Various aspects of the disclosure are provided below.
[0144] The present disclosure provides a synthetic method for preparing a first water-soluble polymer, comprising: polymerizing a backbone unit and at least one mucin binding unit under inverse miniemulsion conditions using a photoinitiator polymer to form a first water-soluble polymer. The method is a catalyst-free multiphase process mediated by low-intensity ultraviolet radiation. The method is a continuous process. The method is an intermittent flow process. The heterogeneous inverse miniemulsion process includes one of the following features: (1) the ability to prepare high molecular weight water-compatible polymers in a low viscosity, high solids form; (2) forming an oil-in-water emulsion of an aqueous solution of a vinyl monomer in an inert hydrocarbon liquid organic dispersion medium; (3) forming droplets with a particle size in the range of 50-500 nm; or (4) free radical polymerization of the monomer in the dispersion medium to form polymer droplets. The first water-soluble polymer has a molecular weight of about 10 kDa to 10,000 kDa, wherein the first water-soluble polymer comprises a plurality of backbone units and at least one first type of mucin binding unit, wherein the backbone units comprise greater than 50% of the first water-soluble polymer based on molecular weight, wherein the first type of mucin binding unit comprises at most 50% of one unit of the first water-soluble polymer based on molecular weight, wherein the first type of mucin binding unit is functionalized such that the water-soluble polymer has a property of altering hydration, rheology, or both of a mucin polymer, a second water-soluble polymer, or a combination thereof, wherein altering hydration, rheology, or both is achieved by mucoadhesion, mucoadhesion, mucoadhesion, mucoadhesion, or a combination thereof. The main chain unit comprises a monomer unit and a copolymer comprising a monomer unit, wherein the monomer unit is selected from: acrylamide monomer, methacrylamide monomer, acrylate monomer, methacrylate monomer, styrene monomer, vinyl pyridine monomer, maleimide monomer, maleic anhydride derived monomer, vinyl ester monomer, vinyl ether monomer, vinyl amide monomer, vinyl amine monomer, vinyl halide monomer, substituted acrylamide, substituted methacrylamide, or a derivative of any of these monomers. The main chain unit comprises a monomer unit or a copolymer comprising a monomer unit, wherein the monomer unit is selected from: acrylamide, N,N-dimethylacrylamide, N,N-dialkylacrylamide, N-alkylacrylamide, N,N-dialkylmethacrylamide, N-alkylmethacrylamide, poly(ethylene glycol)acrylate, poly(ethylene glycol)methacrylate, poly(ethylene glycol)acrylamide and poly(ethylene glycol)methacrylamide. The main chain unit is N,N-dimethylacrylamide. The main chain unit is N-hydroxyethylacrylamide having the following structure: wherein n is 1 to 10, wherein R is a hydroxyl group, an amine group, a carboxylic acid group or a sulfonic acid group, wherein R' is C1 to C 18Straight or branched alkyl. The first water-soluble polymer has a linear or nonlinear structure selected from star, branched, hyperbranched, cyclic, schematically structured copolymers or bottle brushes. The first water-soluble polymer has a nonlinear structure selected from branched or hyperbranched. The mucin binding unit comprises a monomer unit or a copolymer comprising the monomer unit, wherein the monomer unit is selected from: acrylic acid, methacrylic acid, 4-vinylbenzoic acid, 4-(acrylamide)phenylboronic acid, 3-(acrylamide)phenylboronic acid, 2-(acrylamide)phenylboronic acid, 4-vinylphenylboronic acid, 3-vinylphenylboronic acid, 2-vinylphenylboronic acid, 2-(pyridin-2-yldisulfonyl)ethyl methacrylate, pyridinyl disulfide ethyl acrylate, pyridinyl disulfide ethyl acrylamide, pyridinyl disulfide alkyl (e.g., ethyl) methacrylamide, 2-(pyridin-2-yldisulfide alkyl)ethyl acrylate, 2-(pyridin-2-yldisulfide alkyl)ethyl acrylamide, ethyl 2-(pyridin-2-yldisulfanyl)methacrylate, or ethyl 2-(pyridin-2-yldisulfanyl)methacrylate, (4-((2-acrylamidoethyl)carbamoyl)-3-chlorophenyl)boric acid, (4-((2-acrylamidoethyl)carbamoyl)-3-fluorophenyl)boric acid, (4-((2-acrylamidoethyl)carbamoyl)-3-bromophenyl)boric acid, (4-((2-acrylamidoethyl)carbamoyl)-3-iodophenyl)boric acid, a monomer including one or more boronic acid groups, a monomer containing one or more disulfide bond-forming groups, or a derivative of any one of them. The mucin binding unit comprises a monomer unit or a copolymer comprising the monomer unit, wherein the monomer unit comprises a functional group selected from the group consisting of a boronic acid group, a carboxylate group, a carboxylic acid group, a hydrogen bonding group, a hydrophobic group, a 1,2-diol group, a 1,3-diol group, a group capable of forming a disulfide bond, or a derivative of any one thereof.The first water-soluble polymer comprises a second type of mucin-binding unit, wherein the second type of mucin-binding unit comprises a monomer unit or a copolymer comprising the monomer unit, wherein the monomer unit is selected from the group consisting of acrylic acid, methacrylic acid, 4-vinylbenzoic acid, 4-(acrylamide)phenylboronic acid, 3-(acrylamide)phenylboronic acid, 2-(acrylamide)phenylboronic acid, 4-vinylphenylboronic acid, 3-vinylphenylboronic acid, 2-vinylphenylboronic acid, ethyl 2-(pyridin-2-yldisulfonyl)methacrylate, ethyl pyridinyldisulfide acrylate, ethyl pyridinyldisulfide ethylacrylamide, pyridinyldisulfide alkyl (e.g., ethyl)methacrylamide, ethyl 2-(pyridin-2-yldisulfide)acrylate, ethyl 2-(pyridin-2-yldisulfide)acrylate, ethyl 2-(pyridin-2-yldisulfide)meth ... 2-(pyridin-2-yldisulfanyl)ethyl acrylamide, ethyl 2-(pyridin-2-yldisulfanyl)methacrylate, or ethyl 2-(pyridin-2-yldisulfanyl)methacrylate, (4-((2-acrylamidoethyl)carbamoyl)-3-chlorophenyl)boric acid, (4-((2-acrylamidoethyl)carbamoyl)-3-fluorophenyl)boric acid, (4-((2-acrylamidoethyl)carbamoyl)-3-bromophenyl)boric acid, (4-((2-acrylamidoethyl)carbamoyl)-3-iodophenyl)boric acid, a monomer comprising one or more boronic acid groups, a monomer containing one or more disulfide bond forming groups, or a derivative of any of them, wherein the first type of mucin binding unit is different from the second type of mucin binding unit.The first water-soluble polymer comprises a third type of mucin-binding unit, wherein the third type of mucin-binding unit comprises a monomer unit or a copolymer comprising a monomer unit, wherein the monomer unit is selected from the group consisting of acrylic acid, methacrylic acid, 4-vinylbenzoic acid, 4-(acrylamide)phenylboronic acid, 3-(acrylamide)phenylboronic acid, 2-(acrylamide)phenylboronic acid, 4-vinylphenylboronic acid, 3-vinylphenylboronic acid, 2-vinylphenylboronic acid, 2-(pyridin-2-yldisulfonyl)ethyl methacrylate, ethyl pyridinyldithioacrylate, pyridinyldithioethylacrylamide, pyridinyldisulfanylmethacrylamide, ethyl 2-(pyridin-2-yldisulfanyl)acrylate, 2-(pyridin-2-yldisulfanyl)ethylacrylamide, 2-(pyridin-2-yldisulfanyl)methacrylate, or 2-(pyridin-2-yldisulfanyl)ethylacrylamide. disulfide)ethyl methacrylate, (4-((2-acrylamidoethyl)carbamoyl)-3-chlorophenyl)boric acid, (4-((2-acrylamidoethyl)carbamoyl)-3-fluorophenyl)boric acid, (4-((2-acrylamidoethyl)carbamoyl)-3-bromophenyl)boric acid, (4-((2-acrylamidoethyl)carbamoyl)-3-iodophenyl)boric acid, a monomer comprising one or more boronic acid groups, a monomer comprising one or more disulfide bond forming groups, or a derivative of any one thereof, wherein the first type of mucin binding unit is different from the second type of mucin binding unit, wherein the second type of mucin binding unit is different from the third type of mucin binding unit monomer, and the third type of mucin binding unit monomer comprises one or more pyridyl disulfide groups, or a derivative of any one thereof. The first type of mucin binding unit comprises 1 functional unit to about 5% of the first water-soluble polymer (based on molecular weight); wherein the second type of mucin binding unit comprises 1 functional unit to about 5% of the first water-soluble polymer (based on molecular weight); wherein the third type of mucin binding unit comprises 1 functional unit to about 5% of the first water-soluble polymer (based on molecular weight). The first type of mucin binding unit is located only at one or both ends of the first water-soluble polymer. The first water-soluble polymer is a block copolymer. The first water-soluble polymer is a random copolymer. The first water-soluble polymer is a statistical copolymer. The first water-soluble polymer is an alternating copolymer. The first water-soluble polymer is a gradient copolymer. The block copolymer is an AB diblock copolymer or an ABA triblock copolymer, optionally wherein the mucin binding unit is isolated on the A block of the AB diblock copolymer or the A block of the ABA triblock copolymer. The chemical structure of the first water-soluble polymer is as follows:. wherein unit a is a backbone unit and m is greater than 50% of the first water-soluble polymer based on molecular weight, wherein unit b is a first type of mucin-binding unit and n is 1 unit to about 50% of the first water-soluble polymer (based on molecular weight), wherein unit a and unit b are different from each other, R a1 , R a2 , R a3 , R a4 , R b1 , R b2 , R b3 and R b4 Independently of each other, they can be H, -OR1, -NR1R2, -N + (R1)3, -N + (R1)2(R2), -N + (R1)(R2)(R3), -S(O)2R1, -S(O)2OR1, -S(O)2NR1R2, -NR1S(O)2R2, -NR1C(O)R2, -C(O)R1, -C(O)OR1, -C(O)NR1R2, -NR1C(O)OR2, -NR1C(O)NR1R2, -OC(O)NR1R2, -NR1S(O)2NR1R2, -C(O)NR1S(O)2NR1R2, catechol, boronic acid group and pyridyl disulfide group, wherein each R1, R2 and R3 are independently H or linear or branched C 1-18 Alkyl, and -C(O)OCH2CH2-OH, -C(O)OCH2CH2-N(CH3)2, -C(O)OCH2CH2-N + (CH3)3, -C(O)OCH2CH2-OSO3 – , -C(O)OCH2CH2-OSO3H, -C(O)OCH2CH2-SO3 – , -C(O)OCH2CH2-SO3H, and -C(O)N(H)C((CH3)2)CH2SO3 – , -C(O)N(H)C((CH3)2)CH2SO3H, wherein X is C and Y is C. The chemical structure of the first water-soluble polymer is as follows: wherein unit a is a backbone unit and m is greater than 50% of the first water-soluble polymer based on molecular weight, wherein unit b is a first type of mucin-binding unit and n is from 1 unit to about 50% of the first water-soluble polymer based on molecular weight, wherein unit c is a second type of mucin-binding unit and o is from 1 unit to about 50% of the first water-soluble polymer based on molecular weight, wherein unit a and unit b are different from each other, R a1 , R a2 , R a3 , Ra4 , R b1 , R b2 , R b3 and R b4 Independently of each other, they can be H, -OR1, -NR1R2, -N + (R1)3, -N + (R1)2(R2), -N + (R1)(R2)(R3), -S(O)2R1, -S(O)2OR1, -S(O)2NR1R2, -NR1S(O)2R2, -NR1C(O)R2, -C(O)R1, -C(O)OR1, -C(O)NR1R2, -NR1C(O)OR2, -NR1C(O)NR1R2, -OC(O)NR1R2, -NR1S(O)2NR1R2, -C(O)NR1S(O)2NR1R2, catechol, boronic acid group and pyridyl disulfide group, wherein each R1, R2 and R3 are independently H or linear or branched C 1-18 Alkyl, and -C(O)OCH2CH2-OH, -C(O)OCH2CH2-N(CH3)2, -C(O)OCH2CH2-N + (CH3)3, -C(O)OCH2CH2-OSO3 – , -C(O)OCH2CH2-OSO3H, -C(O)OCH2CH2-SO3 – , -C(O)OCH2CH2-SO3H, and -C(O)N(H)C((CH3)2)CH2SO3 – , -C(O)N(H)C((CH3)2)CH2SO3H. wherein X is C, wherein Y is C, wherein Z is C. Unit a, unit b and unit c are different from each other. The chemical structure of the first water-soluble polymer is as follows: wherein unit a is a backbone unit and m is greater than 50% of the first water-soluble polymer based on molecular weight, wherein unit b is a first type of mucin-binding unit and n is from 1 unit to about 50% of the first water-soluble polymer based on molecular weight, wherein unit c is a second type of mucin-binding unit and o is from 1 unit to about 50% of the first water-soluble polymer based on molecular weight, wherein unit d is a second type of mucin-binding unit and o is from 1 unit to about 50% of the first water-soluble polymer based on molecular weight, wherein unit a and unit b are different from each other, R a1 , R a2 , R a3 , R a4 , R b1 , R b2 , R b3 and R b4Independently of each other, they can be H, -OR1, -NR1R2, -N + (R1)3, -N + (R1)2(R2), -N + (R1)(R2)(R3), -S(O)2R1, -S(O)2OR1, -S(O)2NR1R2, -NR1S(O)2R2, -NR1C(O)R2, -C(O)R1, -C(O)OR1, -C(O)NR1R2, -NR1C(O)OR2, -NR1C(O)NR1R2, -OC(O)NR1R2, -NR1S(O)2NR1R2, -C(O)NR1S(O)2NR1R2, catechol, boronic acid group and pyridyl disulfide group, wherein each R1, R2 and R3 are independently H or linear or branched C 1-18 Alkyl, and -C(O)OCH2CH2-OH, -C(O)OCH2CH2-N(CH3)2, -C(O)OCH2CH2-N + (CH3)3, -C(O)OCH2CH2-OSO3 – , -C(O)OCH2CH2-OSO3H, -C(O)OCH2CH2-SO3 – , -C(O)OCH2CH2-SO3H, and -C(O)N(H)C((CH3)2)CH2SO3 – , -C(O)N(H)C((CH3)2)CH2SO3H, wherein X is C, wherein Y is C, wherein Z is C, and wherein Q is C. Unit a, unit b, unit c, and unit d are different from each other. The molecular weight of the first water-soluble polymer is about 100 kDa to 10,000 kDa.
[0145] The present disclosure provides a synthetic method for preparing a branched or hyperbranched first water-soluble polymer, comprising: polymerizing a backbone unit and at least one mucin binding unit to form a branched or hyperbranched first water-soluble polymer, wherein the branched or hyperbranched first water-soluble polymer has a molecular weight of about 10 kDa to 10,000 kDa, wherein the branched or hyperbranched first water-soluble polymer comprises a plurality of backbone units and at least one first type of mucin binding unit, wherein the backbone units account for more than 50% of the first water-soluble polymer based on molecular weight, wherein the first type of mucin binding unit accounts for 1 unit to 50% of the first water-soluble polymer based on molecular weight, wherein the first type of mucin binding unit is functionalized so that the water-soluble polymer has a property of changing the hydration, rheology, or both of the mucin polymer, the second water-soluble polymer, or a combination thereof, wherein changing the hydration, rheology, or both is achieved by mucoadhesion, mucosal plasticity, mucosal integration, or a combination thereof. The polymerization is cationic polymerization, anionic polymerization, ring-opening polymerization, or coordination polymerization. The polymerization is free radical polymerization, conventional free radical polymerization, self-condensing vinyl polymerization (SCVP), reversibly deactivated free radical polymerization, reversible addition-fragmentation chain transfer (RAFT) polymerization, xanthate exchange macromolecular design (MADIX) polymerization, photoinitiator polymerization, atom transfer radical polymerization (ATRP) or stable free radical polymerization (SFRP). When forming a branched or hyperbranched first water-soluble polymer, the backbone unit is the reaction product of a multifunctional water-soluble monomer and a water-soluble monofunctional unit, wherein the mole % of the multifunctional water-soluble monomer is less than 1% relative to the mole % of the monofunctional water-soluble monomer. The monofunctional water-soluble monomer contains one vinyl group or a functional group capable of linear polymerization, and wherein the multifunctional water-soluble monomer contains two or more vinyl groups or functional groups capable of free radical polymerization. The monofunctional water-soluble monomer is selected from N,N-dimethylacrylamide (DMA), N-hydroxyethylacrylamide (HEAm) or 2-methacryloyloxyethylphosphorylcholine (MPC). The monofunctional water-soluble monomer is N,N'-methylenebisacrylamide. The polymerization is self-condensation vinyl polymerization (SCVP) to form a hyperbranched first water-soluble polymer, wherein the main chain unit is the reaction product of a first initiating monomer and a second initiating monomer, wherein the first initiating monomer and the second initiating monomer contain a vinyl group and a group capable of initiating polymerization or capable of being converted into a group capable of initiating polymerization. The first and second initiating monomers are independently selected from the following structures: wherein X is CH3. The degree of branching (DB) of the hyperbranched first water-soluble polymer is greater than 0.4 but less than 1. The degree of branching (DB) of the branched first water-soluble polymer is less than 0.4 but greater than 0. The mucin binding unit comprises a monomer unit or a copolymer comprising the monomer unit, wherein the monomer unit comprises a functional group selected from the group consisting of a boronic acid group, a carboxylate group, a carboxylic acid group, a hydrogen bonding group, a hydrophobic group, a 1,2-diol group, a 1,3-diol group, a group capable of forming a disulfide bond, or a derivative of any one thereof. The mucin binding unit is selected from the group consisting of acrylic acid, methacrylic acid, 4-vinylbenzoic acid, 4-(acrylamide)phenylboronic acid, 3-(acrylamide)phenylboronic acid, 2-(acrylamide)phenylboronic acid, 4-vinylphenylboronic acid, 3-vinylphenylboronic acid, 2-vinylphenylboronic acid, ethyl 2-(pyridin-2-yldisulfonyl)methacrylate, ethyl pyridinyldisulfide acrylate, pyridinyldisulfide ethylacrylamide, pyridinyldisulfide (e.g., ethyl)methacrylamide, ethyl 2-(pyridin-2-yldisulfide)acrylate, 2-(pyridin-2-yldisulfide)ethylacrylamide, 2-(pyridin-2-yldisulfide)ethylacrylamide, The invention relates to a monomer comprising one or more boronic acid groups, a monomer comprising one or more disulfide bond forming groups, or a derivative of any one of them. The mucin binding unit comprises a functional group selected from the group consisting of a boronic acid group, a carboxylate group, a carboxylic acid group, a hydrogen bonding group, a hydrophobic group, a 1,2-diol group, a 1,3-diol group, and a group capable of forming a disulfide bond.
[0146] The present disclosure provides a composition comprising a first branched or hyperbranched water-soluble polymer having a molecular weight of about 10 kDa to 10,000 kDa, wherein the first branched or hyperbranched water-soluble polymer comprises a plurality of backbone units and at least one first type of mucin-binding unit, wherein the backbone units comprise greater than 50% of the first branched or hyperbranched water-soluble polymer based on molecular weight, wherein when forming the branched or hyperbranched first water-soluble polymer, the backbone units are the reaction product of a multifunctional water-soluble monomer and a water-soluble monofunctional unit, wherein the multifunctional water-soluble The mole % of the monofunctional water-soluble monomer is less than 1% relative to the mole % of the monofunctional water-soluble monomer, wherein the first type of mucin binding unit accounts for 1 unit to 50% of the first branched or hyperbranched water-soluble polymer based on molecular weight, wherein the first type of mucin binding unit is functionalized so that the first branched or hyperbranched water-soluble polymer has the property of changing the hydration, rheology or both of the mucin polymer, the second water-soluble polymer or a combination thereof, wherein the change in hydration, rheology or both is achieved by mucoadhesion, mucosal plasticity, mucosal integration or a combination thereof. The monofunctional water-soluble monomer contains one vinyl group or a functional group capable of linear polymerization, and wherein the multifunctional water-soluble monomer contains two or more vinyl groups or functional groups capable of free radical polymerization. The monofunctional water-soluble monomer is selected from N,N-dimethylacrylamide (DMA), N-hydroxyethylacrylamide (HEAm) or 2-methacryloyloxyethylphosphorylcholine (MPC). The monofunctional water-soluble monomer is N,N'-methylenebisacrylamide. The hyperbranched first water-soluble polymer has a degree of branching (DB) greater than 0.4 but less than 1. The branched first water-soluble polymer has a degree of branching (DB) less than 0.4 but greater than 0. The first type of mucin binding unit is located only at one or both ends of the first water-soluble polymer. The first water-soluble polymer is a block copolymer. The first water-soluble polymer is a random copolymer. The first water-soluble polymer is a statistical copolymer. The first water-soluble polymer is an alternating copolymer. The first water-soluble polymer is a gradient copolymer. The block copolymer is an AB diblock copolymer or an ABA triblock copolymer, optionally wherein the mucin binding unit is isolated on the A block of the AB diblock copolymer or the A block of the ABA triblock copolymer. The molecular weight of the first water-soluble polymer is about 100 kDa to 10,000 kDa.
[0147] The present disclosure provides a composition comprising a first branched or hyperbranched water-soluble polymer having a molecular weight of about 10 kDa to 10,000 kDa, wherein the first branched or hyperbranched water-soluble polymer comprises a plurality of backbone units and at least one first type of mucin binding unit, wherein based on molecular weight, the backbone unit comprises greater than 50% of the first branched or hyperbranched water-soluble polymer, wherein the backbone unit is the reaction product of a first initiating monomer and a second initiating monomer, wherein the first initiating monomer and the second initiating monomer contain a vinyl group and a group capable of initiating polymerization or capable of being converted to a group capable of initiating polymerization, wherein based on molecular weight, the first type of mucin binding unit accounts for 1 unit to 50% of the first branched or hyperbranched water-soluble polymer, wherein the first type of mucin binding unit is functionalized so that the first branched or hyperbranched water-soluble polymer has a property of changing the hydration, rheology, or both of the mucin polymer, the second water-soluble polymer, or a combination thereof, wherein changing the hydration, rheology, or both is achieved by mucoadhesion, mucoadhesion, mucoadhesion, mucoadhesion, or a combination thereof. The first initiating monomer and the second initiating monomer are independently selected from the following structures: wherein X is CH3. The degree of branching (DB) of the hyperbranched first water-soluble polymer is greater than 0.4 but less than 1. The degree of branching (DB) of the branched first water-soluble polymer is less than 0.4 but greater than 0. The first type of mucin binding unit is located only at one or both ends of the first water-soluble polymer. The first water-soluble polymer is a block copolymer. The first water-soluble polymer is a random copolymer. The first water-soluble polymer is a statistical copolymer. The first water-soluble polymer is an alternating copolymer. The first water-soluble polymer is a gradient copolymer. The block copolymer is an AB diblock copolymer or an ABA triblock copolymer, optionally wherein the mucin binding unit is isolated on the A block of the AB diblock copolymer or the A block of the ABA triblock copolymer. The molecular weight of the first water-soluble polymer is about 100 kDa to 10,000 kDa.
[0148] The present disclosure provides a composition comprising a first water-soluble polymer having a molecular weight of about 10 kDa to 10,000 kDa, wherein the first water-soluble polymer comprises a plurality of backbone units and at least one first type of mucin binding unit, wherein the backbone units comprise greater than 50% of the first water-soluble polymer based on molecular weight, wherein the first type of mucin binding unit comprises from 1 unit to 50% of the first water-soluble polymer based on molecular weight, wherein the first type of mucin binding unit is functionalized so that the first water-soluble polymer has a property of altering hydration, rheology, or both of a mucin polymer, a second water-soluble polymer, or a combination thereof, wherein altering hydration, rheology, or both is achieved by mucoadhesion, mucoadhesion, mucoadhesion, mucoadhesion, or a combination thereof; wherein the backbone units comprise monomer units and a copolymer comprising the monomer unit, wherein the monomer unit is selected from substituted acrylamide or substituted methacrylamide, or wherein the mucin binding unit comprises a monomer unit or a copolymer comprising the monomer unit, wherein the monomer unit is selected from: (4-((2-acrylamidoethyl)carbamoyl)-3-chlorophenyl)boric acid, (4-((2-acrylamidoethyl)carbamoyl)-3-fluorophenyl)boric acid, (4-((2-acrylamidoethyl)carbamoyl)-3-bromophenyl)boric acid, (4-((2-acrylamidoethyl)carbamoyl)-3-iodophenyl)boric acid, a monomer comprising one or more boronic acid groups, a monomer containing one or more disulfide forming groups, or a derivative of any of these groups, wherein the backbone unit is N-hydroxyethylacrylamide having the following structure: wherein n is 1-10, wherein R is a hydroxyl group, an amine group, a carboxylic acid group or a sulfonic acid group, wherein R' is a C1-C18 straight or branched alkyl group. The backbone unit comprises a monomer unit and a copolymer comprising a monomer unit, wherein the monomer unit is selected from: substituted acrylamide or substituted methacrylamide, wherein the mucin binding unit comprises a monomer unit or a copolymer comprising the monomer unit, wherein the monomer unit is selected from: (4-((2-acrylamidoethyl)carbamoyl)-3-chlorophenyl)boric acid, (4-((2-acrylamidoethyl)carbamoyl)-3-fluorophenyl)boric acid, (4-((2-acrylamidoethyl)carbamoyl)-3-bromophenyl)boric acid, (4-((2-acrylamidoethyl)carbamoyl)-3-iodophenyl)boric acid, a monomer comprising one or more boronic acid groups, a monomer containing one or more disulfide forming groups, or a derivative of any of these groups. The backbone unit comprises a monomer unit and a copolymer comprising the monomer unit, wherein the monomer unit is selected from: a substituted acrylamide or a substituted methacrylamide, and wherein the backbone unit is N-hydroxyethyl acrylamide having the following structure: wherein n is 1 to 10, wherein R is a hydroxyl group, an amine group, a carboxylic acid group or a sulfonic acid group, wherein R' is C1 to C 18 A linear or branched alkyl group. The first water-soluble polymer has a linear or nonlinear structure selected from a star, branched, hyperbranched, cyclic, schematically structured copolymer or a bottle brush. The first type of mucin binding unit is located only at one or both ends of the first water-soluble polymer. The first water-soluble polymer is a block copolymer. The first water-soluble polymer is a random copolymer. The first water-soluble polymer is a statistical copolymer. The first water-soluble polymer is an alternating copolymer. The first water-soluble polymer is a gradient copolymer. The block copolymer is an AB diblock copolymer or an ABA triblock copolymer, optionally wherein the mucin binding unit is isolated on the A block of the AB diblock copolymer or the A block of the ABA triblock copolymer. The molecular weight of the first water-soluble polymer is about 100 kDa to 10,000 kDa.
[0149] Example 1
[0150] We describe the synthesis of ultrahigh molecular weight water-soluble polymers by photoinitiator polymerization under inverse miniemulsion conditions. The catalyst-free multiphase process is mediated by low-intensity UV irradiation and provides fast polymerization rates, excellent molecular weight control, high polymer end-group fidelity, temporal control, advanced architecture, and most notably viscosity control. By considering the properties of surfactants, co-stabilizers, and iniferters, we optimized polymerization conditions to obtain acrylamide homopolymers and block copolymers with molecular weights exceeding 1,000,000 Da at ambient temperature. This approach to well-defined ultrahigh molecular weight polymers overcomes the problem of high viscosity to facilitate eventual scale-up.
[0151] Introduction:
[0152] Heterogeneous polymerization systems account for approximately one fifth of the global polymer production processes. 1-3 The popularity of multiphase polymerization stems from advantages such as viscosity control, improved heat transfer, high propagation rates, and the ability to produce high molecular weight polymers. ,4 These benefits arise primarily from the dispersion of insoluble monomers in stable droplets in a continuous phase, where polymerization occurs at the locus of the droplets and the continuous phase acts as a heat sink for the exothermic polymerization. Importantly, unlike bulk and solution polymerization systems, the viscosity of the emulsion approximates that of the continuous phase and is not significantly affected by the molecular weight of the growing polymer.
[0153] Multiphase polymerization exhibits unique kinetics and rapid propagation rates and remains an active area of research. 1,4-16 Miniemulsion polymerization has attracted much attention due to its enhanced colloidal stability and more uniform droplet size and composition, properties that are associated with improved control of many living polymerization systems. 9,17-20In a miniemulsion, smaller monomer particles are initially formed and serve as polymerization sites. Strong shear is usually required to create high-energy interfaces with particles of 50–500 nm in diameter. 17,21 Therefore, the interface must be stabilized, typically using higher surfactant loadings and the addition of co-stabilizers, to limit monomer diffusion and particle coalescence between droplets. 21 This approach allows miniemulsion monomer droplets to act as nanoreactors for reversible deactivation radical polymerization (RDRP), such as reversible addition–fragmentation chain transfer (RAFT) polymerization, atom transfer radical polymerization (ATRP), and nitroxide-mediated polymerization (NMP). 9,17,22-27 Notably, the enhanced propagation rate and limited termination in these nanoreactors favor the formation of controlled ultrahigh molecular weight polymers. 20,28 This remains a challenge and focus for synthetic polymer chemists. 29-38
[0154] Photoinitiator polymerization is another RDRP technique we use to synthesize well-controlled ultrahigh molecular weight (UHMW) polymers (over 1,000,000 Da). 30,31 Specific reagents that can act as initiators, transfer agents, and terminators have been used to make iniferters and were initially explored for controlled polymer synthesis by Otsu Corporation in the early 1980s. 39,40 The thiocarbonylsulfide photoinitiator (photoinitiator transfer terminator) with the basic structure of ZC(=S)SR undergoes homolytic bond photolysis under visible light or ultraviolet light to generate two free radicals: one can initiate polymerization (R·), and the other acts as a stable free radical that can reversibly terminate (Z(C=)S·), thereby producing a thiocarbonylsulfide end group that allows degenerate chain transfer (Figure 1.1C, schemes A and B). 41 – 47 These polymerization reactions do not require exogenous initiators other than photoinitiators. These systems can also be temporally controlled by simple modulation of light intensity.
[0155] Evidence suggests that both reversible termination and degenerate transfer processes are important for controlling the polymerization process of photoinitiators, with the dominant mechanism varying depending on the structure of the iniferter. 31,48,49 Choose conditions wisely (i.e. high k p monomers, suitable solvents, high monomer concentration, high viscosity, and no exogenous initiator) can provide unprecedented opportunities to increase the polymerization rate (R p ) and the termination rate (R t ) ratio to promote the formation of ultra-high molecular weight substances. 30,31,37,50,51In particular, high viscosity, as a consequence of the synthesis of UHMW polymers, helps to suppress the rate of diffusion-controlled bimolecular reactions (such as termination) and has been shown to be effective in the synthesis of well-targeted UHMW polymers (10 5 -10 7 Unfortunately, the extremely high viscosities that can be achieved with such chain lengths may limit the ultimate scale-up of this approach. Photoinitiator polymerization has been very limitedly explored in (mini)emulsion systems. 25,52-55 However, considering the latter advantage, i.e., the high viscosity is confined to the nanoscale reaction particles, we infer that this approach may have significant potential for the scalable synthesis of ultrahigh molecular weight polymers.
[0156] Here, we present the use of photoinitiator polymerization under inverse miniemulsion conditions to form well-controlled UHMW polymers. The use of a multiphase system limits the viscosity of the entire solution while helping to reduce the polymerization exotherm. Converting photoinitiator polymerization to a miniemulsion system is an important step toward making this UHMW polymer approach more scalable and industrially applicable, potentially facilitating its application in many areas, including the production of flocculants, coacervates, protein mimics, photonic materials, and elastomers. 35,37,46,56-58
[0157] Results and Discussion
[0158] Initially, we sought to explore the effects of various experimental conditions on the synthesis of UHMW (>10 6 Da) poly(N,N-dimethylacrylamide) (PDMA) (Figure 1). We selected reaction components with low UV cutoffs to limit absorption and maximize the photolysis kinetics of the inifert. In addition, it was critical to select a thiocarbonylthio inifert with appropriate water solubility and reactivity to remain in the aqueous phase to effectively promote polymerization. We also sought to identify surfactants and co-stabilizers to provide stable particles of approximately 150 nm in diameter, thereby obtaining UHMW polymers with controlled chain length and dispersity, good chain end fidelity, and control of the on / off times associated with photopolymerization.
[0159] Our initial goal was to form a miniemulsion in which stable water droplets were dispersed in a continuous organic phase as a nanoreactor for DMA polymerization. Cyclohexane was chosen as the continuous organic phase because it is immiscible with water and has low UV absorbance. The dispersed phase consisted of phosphate buffer (PB, pH = 8), N,N-dimethylacrylamide (DMA), 2-(ethylthiocarbonylthiothio)propionic acid (iniferter 1), and internal standard N,N-dimethylformamide (DMF) to allow for the polymerization of DMA by 1Monomer conversion was determined by HNMR spectroscopy. Initially, a [DMA]:[iniferter] ratio of 10,000:1 was selected, with 5 M [DMA] in the aqueous phase, to obtain a well-defined polymer of approximately 1,000,000 Da ( Figure 1.1A ). A miniemulsion was formed by sonicating the reaction components for 15 min.
[0160] Sorbitan monostearate (Span 60) was used as the surfactant for droplet size and stability studies because it is a common surfactant for traditional oil-in-water emulsions. Span 60 has a large 17-carbon hydrophobic tail connected to a small hydrophilic sorbitan head and does not contain unsaturated bonds or UV chromophores that would otherwise interfere with polymerization. Particle size and stability under 18 h of UV irradiation were tested at surfactant loadings of 5, 7.5, 10, 12.5, and 15 wt % (relative to the dispersed phase) (Table S1). Particle size was monitored by dynamic light scattering (DLS) and particles with diameters of 120–140 nm were found over the range of surfactant loadings. However, at lower concentrations of 5 and 7.5 wt % surfactant loadings, significant macroscopic precipitation occurred during polymerization. Very little precipitation was visible at surfactant loadings of 10 and 12.5 wt % and no precipitation was evident at 15 wt % surfactant loading. Span 60 was also blended with another surfactant, Tween 60, in an attempt to improve particle stability (Table S2). However, the addition of Tween 60, a more hydrophilic component, resulted in decreased particle stability, as evidenced by an increase in initial particle size monitored by DLS and eventual macroscopic phase separation. Sodium chloride was also introduced into the system as a co-stabilizer to limit particle instability caused by Ostwald ripening (Table S3). 21 As monitored by DLS in the early stages of polymerization, NaCl was observed to enhance particle stability by reducing droplet dispersion. Table 1 shows sample polymerizations performed using optimized salt and surfactant equivalents.
[0161] Table 1. Optimized conditions for DMA inverse miniemulsion polymerization at 30 °C and 1000 RPM stirring speed
[0162]
[0163]
[0164] a Weight percentage relative to the total mass of monomer and water in the dispersed phase
[0165] like Figure 1.2A As shown, after ultrasonic treatment, the unreacted emulsion is optically transparent ( Figure 1.2A The transparency of the solution depends on the size of the nanoscale droplets in the system ( Figure 1.2B-1.2D), limited solids content and similar refractive indices of cyclohexane and 5MDMA dispersed phases. 1,59 Decreasing the dispersed phase DMA concentration from 5 to 2 M resulted in an opaque solution despite the small droplet size and the same mass ratio of dispersed phase to continuous phase.
[0166] The particle size of the inverse miniemulsion system was studied using transmission electron microscopy (TEM). Figure 1.2C , 1.2D). To ensure the stability of the particles during drop casting and imaging, a crosslinker, N-methylenebisacrylamide (MBA), was added to the model polymerization at a concentration of 8 mol% relative to DMA. The crosslinker produced stable polymer particles suitable for TEM sample preparation. The number average diameter (d N ) is 78 nm, which is different from the 85 nm d measured by DLS. N Relatively consistent.
[0167] Under optimized reverse miniemulsion conditions, ultrahigh molecular weight polymers of about 1,000,000 Da were synthesized using iniferter 1. Figure 1.3A ). Size exclusion chromatography (SEC) data indicated that the synthesis of high molecular weight polymers was more challenging, likely due to chain transfer reactions, presumably associated with the surfactant. Notably, a polymer with a molecular weight of 1,210,000 Da could be obtained by decreasing the temperature from 30 °C to 10 °C, an observation that may be consistent with the occurrence of chain transfer. For all polymerizations, the overall viscosity of the system remained low, and the solutions flowed readily and were easily stirred with a magnetic stir bar ( Figure 1.3B In contrast, the homogeneous aqueous polymerization of DMA in PB pH 8 (conditions similar to the dispersed phase of a miniemulsion) produced a high viscosity solution due to the high concentration of UHMWPDMA ( Figure 1.3C ).
[0168] To further understand the controllable nature of this multiphase polymerization approach, the polymerization mediated by iniferter 1 was studied in more detail (Figure 1.4). For the polymerization reaction with a target molecular weight of 1,000,000 Da at full conversion, the experimental number average molecular weight increased with conversion, and the dispersion remained reasonably stable throughout the polymerization. ( Figure 1.4A , B). In addition, the linear pseudo-first-order kinetics plots indicate that the radical concentration remains constant to achieve high monomer conversion ( Figure 1.4C ). DLS analysis showed that the particle size did not change significantly during the polymerization process ( Figure 1.4D ), as expected for a miniemulsion system, although a slight (and reversible) increase in particle size was consistently observed at lower conversions.
[0169] Photoinitiator polymerization is controlled by a combination of reversible termination and degenerative chain transfer. 31,48,49 and must be considered when selecting an iniferter for a given set of polymerization conditions. Therefore, we explored other iniferters to determine the effect on polymerization control under reverse miniemulsion conditions (Figures 5A, 5B, S9-S13). For an iniferter to effectively initiate and mediate polymerization in aqueous media, it must be stable to hydrolysis and have sufficient water solubility to effectively partition to the polymerization site (i.e., the droplet containing water and monomer). 17,60,61
[0170] UV-Vis spectroscopy was used to monitor the iniferters 1-4 ( Figure 1.5A ) because hydrolysis of the trithiocarbonate can have a deleterious effect on polymerization control. 17,62,63 The UV absorption spectra and molar extinction coefficients of each iniferter in PB were determined. Iniferters 1-4 were dissolved in PB and monitored by UV-visible spectroscopy for 18 h, during which time there was no change in the UV absorbance of iniferters 1, 2, or 4; however, the absorbance of iniferter 3 showed a slight decrease, which may be caused by hydrolysis. 62,63 The partitioning behavior of the iniferter in water / cyclohexane mixtures was monitored by UV-vis spectroscopy. Figure 1.5C , 1.5D). The UV absorbance of iniferters 1-4 in PB was measured before and after the introduction of cyclohexane at concentrations relevant to the polymerization conditions. In the absence of UV irradiation (simulating the polymerization system before initiation), there was no significant change in the UV absorbance of the iniferters after the addition of the iniferters and mixing with cyclohexane. These results indicate that the iniferters are well distributed in the aqueous phase ( Figure 1.5C When the biphasic reaction solution was exposed to ultraviolet light (simulating the initial polymerization system), the absorbance of all iniferters in the aqueous phase decreased, indicating the loss of intact iniferters or the decrease in the concentration of thiocarbonylthio fragments of iniferters after homolytic bond cleavage ( Figure 1.5D Interestingly, the absorbance intensity decreases of iniferters 2 and 3 upon UV irradiation were slightly smaller, which may be due to their carboxylate Z groups, which may indicate that the sulfur-centered thiocarbonylthio group with a polar substituent is more likely to remain within the aqueous polymerization site after cleavage of the C-S bond by photolysis.
[0171] The rate of photoinitiator polymerization depends primarily on the nature of the light-absorbing thiocarbonylthio moiety in the photoinitiator, i.e., trithiocarbonate (1-3) or xanthate (4) ( Figure 1.5E ). Water-soluble trithiocarbonates 1-3 produced similar rates of polymerization ( Figure 1.5E ) and allows the synthesis of ultrahigh molecular weight polymers in a controlled manner (Figures 1.4, 1.5F), the number average molecular weight of the polymer increases linearly with the monomer conversion, and this is evidenced by the relatively narrow molecular weight distribution observed by SEC. The R and Z groups of the iniferter 3 contain carboxyl groups, which can improve its solubility in the aqueous phase, thus achieving polymerization control and molecular weight in the range of 10 6 The best combinations were found in the Da range (Table 2). The thiocarbonylthio Z group of inifert 3 improves solubility at the polymerization site, which may help limit the loss of photogenerated thiocarbonylthio groups to the organic phase. However, when the target M n Value greater than 2×10 6 Da, the polymerization control is weakened. Given our previous observations, when carried out in homogeneous aqueous media, this type of trithiocarbonate can be M n Close to 5×10 6 The PDMA of Da provides channels, an observation that may again indicate that chain transfer to the surfactant poses a problem, although running the polymerization at a lower temperature of 10 °C did not significantly improve control in this case.
[0172] Iniferter 4, a hydrophilic xanthate, failed to achieve controlled polymerization and exhibited M n unchanged, the conversion rate increases ( Figure 1.5F ). Xanthates undergo rapid photoexcitation and photolysis, and previous studies have shown that they can act as iniferters to efficiently form UHMW polymers in a controlled manner. 31 However, the chain transfer constant for xanthate to PDMA is relatively low, suggesting that reversible termination plays a more important role in deactivation compared to initiation of DMA polymerization using trithiocarbonates. 31,48 The loss of control under miniemulsion conditions may indicate that the transfer of the thiocarbonylthio group of iniferter 4 into the organic phase may affect the effectiveness of reversible termination.
[0173] Table 2. Reverse miniemulsion photopolymerization using iniferter 3.
[0174]
[0175]
[0176] All polymerizations lasted for 12 hours. a Polymerization temperature. b pass 1 Monomer conversion was determined by H NMR spectroscopy. c Theoretical number average molecular weight. d Experimental number average molecular weight determined by SEC. eFinal polymer chain dispersion. f The hydrodynamic diameter of the inverse miniemulsion particles before polymerization, measured by DLS. g The hydrodynamic diameter of the inverse miniemulsion particles after polymerization, measured by DLS.
[0177] The polymerization kinetics demonstrated that the reverse miniemulsion polymerization of DMA mediated by trithiocarbonate iniferters 1 and 3 was well controlled (Figures 1.4, 1.5), and is expected to produce polymers with high end base fidelity. To verify the chain end retention under reverse miniemulsion conditions, PDMA prepared with iniferters 1 and 3 was in situ extended using additional DMA or 4-acryloylmorpholine (NMO) to synthesize a second block with a target molecular weight of 1,000,000 Da (Figure 1.6). These block copolymerizations were carried out in a one-pot process, where a PB solution of the second monomer was added to the system when the initial PDMA homopolymer synthesis reached about 85+% monomer conversion. DLS measurements showed that the polymer particles swelled with the addition of solvent and monomer. During the addition of the second block, the SEC curve of the original PDMA clearly shifted to a higher molecular weight, indicating good chain end retention.
[0178] Finally, we demonstrated that typical temporal control of photopolymerization is conferred to this inverse miniemulsion polymerization system (Fig. 1.7). Photoexcitation of ions and radical formation occur only when the light source is turned on. For DMA polymerization mediated by iniferter 1 under the conditions described in Table 1, almost no monomer conversion was observed when the light was turned off, and the molecular weight increased only with increasing conversion during irradiation ( Figure 1.7A , C). The particle size remained constant throughout the on-off light cycle, indicating that the aggregated particles remained stable in the dark for more than 16 h ( Figure 1.7D ).
[0179] in conclusion
[0180] The inverse miniemulsion system we designed serves as a model for the synthesis of well-controlled UHMW PDMA via photoinitiator polymerization. The effects of reaction parameters such as surfactant loading, salt concentration, and iniferter identity all play an important role in controlling droplet size and enhancing molecular weight control. By appropriate choice of miniemulsion components, PDMA with molecular weights exceeding 1,000,000 Da can be rapidly synthesized in solutions that maintain low viscosity. The UHMW polymers retain a high degree of chain-end fidelity, as demonstrated by in situ chain extension, generating UHMW block copolymers without the need for intermediate purification. Overall, the use of photoinitiator polymerization in a miniemulsion system is an important step toward the scale-up of UHMW materials with controlled molecular weight, chain-end retention, and complex architectures. Ongoing work in our laboratory is focused on increasing the molecular weight range that can be achieved with this approach.
[0181] References for Example 1
[0182] (1) Jasinski, F.;Zetterlund, P. B.;Braun, A. M.;Chemtob, A. Photopolymerization in Dispersed Systems. Prog. Polym. Sci. 2018, 84, 47–88. https: / / doi.org / 10.1016 / j.progpolymsci.2018.06.006.
[0183] (2) Dinsmore, R. P. Synthetic Rubber and Method of Making It. US1732795A, October 22, 1929.
[0184] (3) Odian, G. Emulsion Polymerization. In Principles of Polymerization. McGraw-Hill, Inc. 1970;pp 279–300.
[0185] (4) Khan, M.; T. R.;Zhou, D.;Moad, G.;Perrier, S.;Zetterlund, P. B. Exploitation of Compartmentalization in RAFT Miniemulsion Polymerization to Increase the Degree of Livingness. J. Polym. Sci. Part A Polym. Chem. 2019, 57, 1938–1946. https: / / doi.org / 10.1002 / pola.29329.
[0186] (5)Touve,M.A.;Figg,C.A.;Wright,D.B.;Park,C.;Cantlon,J.;Sumerlin,B.S.;Gianneschi,N.C.Polymerization-Induced Self-Assembly of Micelles Observed byLiquid Cell Transmission Electron Microscopy.ACS Cent.Sci.2018,4,543–547.https: / / doi.org / 10.1021 / acscentsci.8b00148.
[0187] (6)Figg,C.A.;Simula,A.;Gebre,K.A.;Tucker,B.S.;Haddleton,D.M.;Sumerlin,B.S.Polymerization-Induced Thermal Self-Assembly(PITSA).Chem.Sci.2015,6,1230–1236.https: / / doi.org / 10.1039 / C4SC03334E.
[0188] (7)Tan,J.;Sun,H.;Yu,M.;Sumerlin,B.S.;Zhang,L.Photo-PISA:SheddingLight on Polymerization-Induced Self-Assembly.ACS Macro Lett.2015,4,1249–1253.https: / / doi.org / 10.1021 / acsmacrolett.5b00748.
[0189] (8)O’Bryan,C.S.;Kabb,C.P.;Sumerlin,B.S.;Angelini,T.E.JammedPolyelectrolyte Microgels for 3D Cell Culture Applications:RheologicalBehavior with Added Salts.ACS Appl.Bio Mater.2019,2,1509–1517.https: / / doi.org / 10.1021 / acsabm.8b00784.
[0190] (9)Zetterlund,P.B.;Kagawa,Y.;Okubo,M.Controlled / Living RadicalPolymerization in Dispersed Systems.Chem.Rev.2008,108,3747–3794.https: / / doi.org / 10.1021 / cr800242x.
[0191] (10)Turro,N.J.;Chow,M.-F.;Chung,C.-J.;Tung,C.-H.An Efficient,HighConversion Photoinduced Emulsion Polymerization.Magnetic Field Effects onPolymerization Efficiency and Polymer Molecular Weight.J.Am.Chem.Soc.1980,102,7391–7393.https: / / doi.org / 10.1021 / ja00544a053.
[0192] (11)Bianchi,J.P.;Price,F.P.;Zimm,B.H.“Monodisperse”Polystyrene.J.Polym.Sci.1957,25,27–38.https: / / doi.org / 10.1002 / pol.1957.1202510803.
[0193] (12)Tobita,H.Effect of Small Reaction Locus in Free-RadicalPolymerization:Conventional and Reversible-Deactivation Radical Polymerization.Polymers.2016.https: / / doi.org / 10.3390 / polym8040155.
[0194] (13)Khan,M.; T.R.;Choong,K.;Moad,G.;Perrier,S.;Zetterlund,P.B.RAFT Emulsion Polymerization for(Multi)Block Copolymer Synthesis:Overcoming the Constraints of Monomer Order.Macromolecules 2021,54,736–746.https: / / doi.org / 10.1021 / acs.macromol.0c02415.
[0195] (14)Richardson,R.A.E.; T.R.;Khan,M.;Moad,G.;Zetterlund,P.B.;Perrier,S.Low-Dispersity Polymers in Ab Initio Emulsion Polymerization:Improved MacroRAFT Agent Performance in Heterogeneous Media.Macromolecules2020,53,7672–7683.https: / / doi.org / 10.1021 / acs.macromol.0c01311.
[0196] (15)Rho,J.Y.;Scheutz,G.M.; S.;Garrison,J.B.;Song,Q.;Yang,J.;Richardson,R.;Perrier,S.;Sumerlin,B.S.In Situ Monitoring of PISAMorphologies.Polym.Chem.2021,12,3947–3952.https: / / doi.org / 10.1039 / D1PY00239B.
[0197] (16)Scheutz,G.M.;Touve,M.A.;Carlini,A.S.;Garrison,J.B.;Gnanasekaran,K.;Sumerlin,B.S.;Gianneschi,N.C.Probing Thermoresponsive Polymerization-Induced Self-Assembly with Variable-Temperature Liquid-Cell TransmissionElectron Microscopy.Matter 2021,4,722–736.https: / / doi.org / 10.1016 / j.matt.2020.11.017.
[0198] (17)Qi,G.;Jones,C.W.;Schork,F.J.RAFT Inverse MiniemulsionPolymerization of Acrylamide.Macromol.Rapid Commun.2007,28,1010–1016.https: / / doi.org / 10.1002 / marc.200700026.
[0199] (18)Ferguson,C.J.;Hughes,R.J.;Nguyen,D.;Pham,B.T.T.;Gilbert,R.G.;Serelis,A.K.;Such,C.H.;Hawkett,B.S.Ab Initio Emulsion Polymerization by RAFT-Controlled Self-Assembly.Macromolecules 2005,38,2191–2204.https: / / doi.org / 10.1021 / ma048787r.
[0200] (19)Ferguson,C.J.;Hughes,R.J.;Pham,B.T.T.;Hawkett,B.S.;Gilbert,R.G.;Serelis,A.K.;Such,C.H.Effective Ab Initio Emulsion Polymerization under RAFTControl.Macromolecules 2002,35,9243–9245.https: / / doi.org / 10.1021 / ma025626j.
[0201] (20)Simms,R.W.;Cunningham,M.F.High Molecular Weight Poly(ButylMethacrylate)by Reverse Atom Transfer Radical Polymerization in MiniemulsionInitiated by a Redox System.Macromolecules 2007,40,860–866.https: / / doi.org / 10.1021 / ma061899t.
[0202] (21)Asua,J.M.Miniemulsion Polymerization.Progress in Polymer Science(Oxford).Elsevier Ltd 2002,pp 1283–1346.https: / / doi.org / 10.1016 / S0079-6700(02)00010-2.
[0203] (22)Oh,J.K.;Tang,C.;Gao,H.;Tsarevsky,N.V;Matyjaszewski,K.InverseMiniemulsion ATRP:A New Method for Synthesis and Functionalization of Well-Defined Water-Soluble / Cross-Linked Polymeric Particles.J.Am.Chem.Soc.2006,128,5578–5584.https: / / doi.org / 10.1021 / ja060586a.
[0204] (23)Qi,G.;Eleazer,B.;W.Jones,C.;Joseph Schork,F.Mechanistic Aspectsof Sterically Stabilized Controlled Radical Inverse MiniemulsionPolymerization.Macromolecules 2009,42,3906–3916.https: / / doi.org / 10.1021 / ma802741u.
[0205] (24)Zetterlund,P.B.;Okubo,M.Compartmentalization in Nitroxide-Mediated Radical Polymerization in Dispersed Systems.Macromolecules 2006,39,8959–8967.https: / / doi.org / 10.1021 / ma060841b.
[0206] (25)Tonnar,J.;Pouget,E.;Lacroix-Desmazes,P.;Boutevin,B.Synthesis ofPoly(Vinyl Acetate)-Block-Poly(Dimethylsiloxane)-Block-Poly(Vinyl Acetate)Copolymers by Iodine Transfer Photopolymerization inMiniemulsion.Macromol.Symp.2009,281,20–30.https: / / doi.org / 10.1002 / masy.200950703.
[0207] (26)Fan,W.;Tosaka,M.;Yamago,S.;Cunningham,M.F.Living Ab InitioEmulsion Polymerization of Methyl Methacrylate in Water Using a Water-SolubleOrganotellurium Chain Transfer Agent under Thermal and PhotochemicalConditions.Angew.Chemie Int.Ed.2018,57,962–966.https: / / doi.org / 10.1002 / anie.201710754.
[0208] (27)Detrembleur,C.;Debuigne,A.;Bryaskova,R.;Charleux,B.; R.Cobalt-Mediated Radical Polymerization of Vinyl Acetate in Miniemulsion:Very Fast Formation ofStable Poly(Vinyl Acetate)Latexes at LowTemperature.Macromol.Rapid Commun.2006,27,37–41.https: / / doi.org / 10.1002 / marc.200500645.
[0209] (28)Truong,N.P.;Dussert,M.V;Whittaker,M.R.;Quinn,J.F.;Davis,T.P.RapidSynthesis of Ultrahigh Molecular Weight and Low Polydispersity PolystyreneDiblock Copolymers by RAFT-Mediated Emulsion Polymerization.Polym.Chem.2015,6,3865–3874.https: / / doi.org / 10.1039 / C5PY00166H.
[0210] (29)Li,S.;Han,G.;Zhang,W.Photoregulated Reversible Addition–Fragmentation Chain Transfer(RAFT)Polymerization.Polym.Chem.2020,11,1830–1844.https: / / doi.org / 10.1039 / D0PY00054J.
[0211] (30)Nicholas Carmean,R.;B.Sims,M.;Adrian Figg,C.;J.Hurst,P.;P.Patterson,J.;S.Sumerlin,B.Ultrahigh Molecular Weight Hydrophobic Acrylicand Styrenic Polymers through Organic-Phase Photoiniferter-MediatedPolymerization.ACS Macro Lett.2020,9,613–618.https: / / doi.org / 10.1021 / acsmacrolett.0c00203.
[0212] (31)Carmean,R.N.;Becker,T.E.;Sims,M.B.;Sumerlin,B.S.Ultra-HighMolecular Weights via Aqueous Reversible-Deactivation RadicalPolymerization.Chem 2017,2,93–101.https: / / doi.org / 10.1016 / j.chempr.2016.12.007.
[0213] (32)Percec,V.;Guliashvili,T.;Ladislaw,J.S.;Wistrand,A.;Stjerndahl,A.;Sienkowska,M.J.;Monteiro,M.J.;Sahoo,S.Ultrafast Synthesis ofUltrahigh MolarMass Polymers by Metal-Catalyzed Living Radical Polymerization of Acrylates,Methacrylates,and Vinyl Chloride Mediated by SET at 25℃.J.Am.Chem.Soc.2006,128,14156–14165.https: / / doi.org / 10.1021 / ja065484z.
[0214] (33) R.;Kwak,Y.;Matyjaszewski,K.A Green Route to Well-DefinedHigh-Molecular-Weight(Co)Polymers Using ARGET ATRP with Alkyl Pseudohalidesand Copper Catalysis.Angew.Chemie Int.Ed.2010,49,541–544.https: / / doi.org / 10.1002 / anie.200905340.
[0215] (34)Read,E.;Guinaudeau,A.;James Wilson,D.;Cadix,A.;Violleau,F.;Destarac,M.Low Temperature RAFT / MADIX Gel Polymerisation:Access to ControlledUltra-High Molar Mass Polyacrylamides.Polym.Chem.2014,5,2202–2207.https: / / doi.org / 10.1039 / C3PY01750H.
[0216] (35)Hayashi,M.;Noro,A.;Matsushita,Y.Highly Extensible SupramolecularElastomers with Large Stress Generation Capability Originating from MultipleHydrogen Bonds on the Long Soft Network Strands.Macromol.Rapid Commun.2016,37,678–684.https: / / doi.org / 10.1002 / marc.201500663.
[0217] (36)Liu,Z.;Lv,Y.;An,Z.Enzymatic Cascade Catalysis for the Synthesisof Multiblock and Ultrahigh-Molecular-Weight Polymers with OxygenTolerance.Angew.Chemie Int.Ed.2017,56,13852–13856.https: / / doi.org / 10.1002 / anie.201707993.
[0218] (37)An,Z.100th Anniversary of Macromolecular Science Viewpoint:Achieving Ultrahigh Molecular Weights with Reversible Deactivation RadicalPolymerization.ACS Macro Lett.2020,9,350–357.https: / / doi.org / 10.1021 / acsmacrolett.0c00043.
[0219] (38)Rzayev,J.;Penelle,J.HP-RAFT:A Free-Radical PolymerizationTechnique for Obtaining Living Polymers of Ultrahigh MolecularWeights.Angew.Chemie Int.Ed.2004,43,1691–1694.https: / / doi.org / 10.1002 / anie.200353025.
[0220] (39)Otsu,T.;Yoshida,M.Role of Initiator-Transfer Agent-Terminator(Iniferter)in Radical Polymerizations:Polymer Design by Organic Disulfides asIniferters.Die Makromol.Chemie,Rapid Commun.1982,3,127–132.https: / / doi.org / 10.1002 / marc.1982.030030208.
[0221] (40)Otsu,T.Iniferter Concept and Living RadicalPolymerization.J.Polym.Sci.Part A Polym.Chem.2000,38,2121–2136.https: / / doi.org / 10.1002 / (SICI)1099-0518(20000615)38:12<2121::AID-POLA10>3.0.CO;2-X.
[0222] (41)Thum,M.D.;Wolf,S.;Falvey,D.E.State-Dependent Photochemical andPhotophysical Behavior of Dithiolate Ester and Trithiocarbonate ReversibleAddition–Fragmentation Chain Transfer Polymerization Agents.J.Phys.Chem.A2020,124,4211–4222.https: / / doi.org / 10.1021 / acs.jpca.0c02678.
[0223] (42)McKenzie,T.G.;Fu,Q.;Wong,E.H.H.;Dunstan,D.E.;Qiao,G.G.VisibleLight Mediated Controlled Radical Polymerization in the Absence of ExogenousRadical Sources or Catalysts.Macromolecules 2015,48,3864–3872.https: / / doi.org / 10.1021 / acs.macromol.5b00965.
[0224] (43)Otsu,T.;Matsunaga,T.;Kuriyama,A.;Yoshioka,M.Living RadicalPolymerization through the Use of Iniferters:Controlled Synthesis ofPolymers.Eur.Polym.J.1989,25,643–650.https: / / doi.org / 10.1016 / 0014-3057(89)90023-2.
[0225] (44)You,Y.-Z.;Hong,C.-Y.;Bai,R.-K.;Pan,C.-Y.;Wang,J.Photo-InitiatedLiving Free Radical Polymerization in the Presence of Dibenzyl Trithiocarbonate.Macromol.Chem.Phys.2002,203,477–483.https: / / doi.org / 10.1002 / 1521-3935(20020201)203:3<477::AID-MACP477>3.0.CO;2-M.
[0226] (45)Xu,J.;Shanmugam,S.;Corrigan,N.A.;Boyer,C.Catalyst-Free VisibleLight-Induced RAFT Photopolymerization.In Controlled Radical Polymerization:Mechanisms;ACS Symposium Series;American Chemical Society,2015;Vol.1187,pp13–247.https: / / doi.org / doi:10.1021 / bk-2015-1187.ch013.
[0227] (46)Liu,Y.;F.Santa Chalarca,C.;Nicholas Carmean,R.;A.Olson,R.;Madinya,J.;S.Sumerlin,B.;E.Sing,C.;Emrick,T.;L.Perry,S.Effect of PolymerChemistry on the Linear Viscoelasticity of Complex Coacervates.Macromolecules2020,7851–7864.https: / / doi.org / 10.1021 / acs.macromol.0c00758.
[0228] (47)Carmean,R.N.;Figg,C.A.;Scheutz,G.M.;Kubo,T.;Sumerlin,B.S.Catalyst-Free Photoinduced End-Group Removal of ThiocarbonylthioFunctionality.ACS Macro Lett.2017,6,185–189.https: / / doi.org / 10.1021 / acsmacrolett.7b00038.
[0229] (48)Easterling,C.P.;Xia,Y.;Zhao,J.;Fanucci,G.E.;Sumerlin,B.S.BlockCopolymer Sequence Inversion through Photoiniferter Polymerization.ACS MacroLett.2019,8,1461–1466.https: / / doi.org / 10.1021 / acsmacrolett.9b00716.
[0230] (49)Quinn,J.F.;Barner,L.;Barner-Kowollik,C.;Rizzardo,E.;Davis,T.P.Reversible Addition-Fragmentation Chain Transfer Polymerization Initiatedwith Ultraviolet Radiation.Macromolecules 2002,35,7620–7627.https: / / doi.org / 10.1021 / ma0204296.
[0231] (50)Storey,R.F.Fundamental Aspects of Living Polymerization.InFundamentals of Controlled / Living Radical Polymerization;The Royal Society ofChemistry,2013;pp 60–77.https: / / doi.org / 10.1039 / 9781849737425-00060.
[0232] (51)Matyjaszewski,K.Ranking Living Systems.Macromolecules 1993,26,1787–1788.https: / / doi.org / 10.1021 / ma00059a048.
[0233] (52)Shim,S.E.;Shin,Y.;Jun,J.W.;Lee,K.;Jung,H.;Choe,S.Living-Free-Radical Emulsion Photopolymerization ofMethyl Methacrylate by a SurfaceActive Iniferter(Suriniferter).Macromolecules 2003,36,7994–8000.https: / / doi.org / 10.1021 / ma034331i.
[0234] (53)Zhao,M.;Zhang,H.;Ma,F.;Zhang,Y.;Guo,X.;Zhang,H.EfficientSynthesis of Monodisperse,Highly Crosslinked,and“Living”Functional PolymerMicrospheres by the Ambient Temperature Iniferter-Induced“Living”RadicalPrecipitation Polymerization.J.Polym.Sci.Part A Polym.Chem.2013,51,1983–1998.https: / / doi.org / 10.1002 / pola.26579.
[0235] (54)Li,J.;Zu,B.;Zhang,Y.;Guo,X.;Zhang,H.One-Pot Synthesis of Surface-Functionalized Molecularly Imprinted Polymer Microspheres by Iniferter-Induced“Living”Radical Precipitation Polymerization.J.Polym.Sci.PartAPolym.Chem.2010,48,3217–3228.https: / / doi.org / 10.1002 / pola.24057.
[0236] (55)Kwak,J.;Lacroix-Desmazes,P.;Robin,J.J.;Boutevin,B.;Torres,N.Synthesis of Mono Functional Carboxylic Acid Poly(Methyl Methacrylate)inAqueous Medium Using Sur-Iniferter.Application to the Synthesis of GraftCopolymers Polyethylene-g-Poly(Methyl Methacrylate)and the Compatibilizationof LDPE / PVDF Blends.Polymer.2003,44,5119–5130.https: / / doi.org / 10.1016 / S0032-3861(03)00525-1.
[0237] (56)Mapas,J.K.D.;Thomay,T.;Cartwright,A.N.;Ilavsky,J.;Rzayev,J.Ultrahigh Molecular Weight Linear Block Copolymers:Rapid Access byReversible-Deactivation Radical Polymerization and Self-Assembly into LargeDomain Nanostructures.Macromolecules 2016,49,3733–3738.https: / / doi.org / 10.1021 / acs.macromol.6b00863.
[0238] (57)Dao,V.H.;Cameron,N.R.;Saito,K.Synthesis of UHMW Star-Shaped ABBlock Copolymers and Their Flocculation Efficiency in High-Ionic-StrengthEnvironments.Macromolecules 2019,52,7613–7624.https: / / doi.org / 10.1021 / acs.macromol.9b01290.
[0239] (58)Plucinski,A.;Pavlovic,M.;Schmidt,B.V.K.J.All-Aqueous Multi-PhaseSystems and Emulsions Formed via Low-Concentration Ultra-High-Molar MassPolyacrylamides.Macromolecules 2021,54,5366–5375.https: / / doi.org / 10.1021 / acs.macromol.1c00400.
[0240] (59)Sun,J.Z.;Erickson,M.C.E.;Parr,J.W.Refractive Index Matching andClear Emulsions.J.Cosmet.Sci.2005,56,253–265.
[0241] (60)Jung,K.;Boyer,C.;Zetterlund,P.B.RAFT Iniferter Polymerization inMiniemulsion Using Visible Light.Polym.Chem.2017,8,3965–3970.https: / / doi.org / 10.1039 / C7PY00939A.
[0242] (61) T.R.;Bong,Y.L.;Thompson,S.W.;Moad,G.;Perrier,S.;Zetterlund,P.B.Polymerization-Induced Self-Assembly via RAFT in Emulsion:Effect of Z-Group on the Nucleation Step.Polym.Chem.2021,12,122–133.https: / / doi.org / 10.1039 / D0PY01311K.
[0243] (62) B. Thomas, D.; J. Convertine, A.; D. Hester, R.; B. Lowe, A.; L. McCormick, C. Hydrolytic Susceptibility of Dithioester Chain Transfer Agents and Implications in Aqueous RAFT Polymerizations. Macromolecules 2004,37,1735–1741. https: / / doi.org / 10.1021 / ma035572t.
[0244] (63) V. Fuchs, A.; J. Thurecht, K. Stability of Trithiocarbonate RAFT AgentsContaining Both a Cyano and a Carboxylic Acid Functional Group. ACS MacroLett. 2017, 6, 287–291. https: / / doi.org / 10.1021 / acsmacrolett.7b00100.
[0245] Example 2
[0246] This example describes the first successful controlled synthesis of more than 10 6 g / mol of ultrahigh molecular weight (UHMW) polymers. At high conversions, homogeneous UHMW batch polymerizations exhibit high viscosities, which pose a challenge for continuous flow reactors. However, under multiphase inverse miniemulsion (IME) conditions, UHMW polymers can be obtained in the dispersed phase, while the viscosity of the multiphase solution remains approximately the same as that of the continuous phase. In this paper, we discuss the kinetics of UHMW IME polymerizations carried out in flow and explore the range of molecular weights that can be obtained using this approach. Furthermore, we find that UHMW IME polymerizations carried out in flow show a significant increase in rate compared to both batch solution polymerization and IME polymerization, while still displaying excellent controllability.
[0247] introduction
[0248] In the decades since its discovery, reversible deactivation radical polymerization (RDRP) has been used to obtain polymers for applications in biomedicine, energy, and informatics. 1–8 The ability to precisely tune macromolecular properties (e.g., molecular weight, structure, functionality) enables the deployment of RDRP for the synthesis of advanced materials over a wide range of size scales.9–16 Although a predetermined molecular weight is a defining feature of RDRP methods such as atom transfer radical polymerization (ATRP), nitroxide-mediated polymerization (NMP), and reversible addition-fragmentation chain transfer (RAFT) polymerization, the target molecular weight of more than 10 6 g / mol, and often require special reaction conditions such as high pressure. 17–25 However, recent studies on RDRP have opened up a new synthetic route for controlling ultrahigh chain-length polymer materials using mild conditions. 26 We recently demonstrated that in water there are p ) vinyl monomers, long-wave ultraviolet (UV) irradiation of thiocarbonylsulfide compounds can produce ultra-high molecular weight (UHMW) polymers with predictable molecular weights. 27 In photoinitiator polymerization, 28 The thiocarbonylsulfide compounds act as photoinitiators, chain transfer agents, and chain terminators. Importantly, this method does not require the exogenous free radical initiators used in RAFT polymerization. The lack of exogenous free radical initiators is critical to accessing UHMW because the constant background generation of low molecular weight radicals through bimolecular coupling in RAFT limits the chain length. Since this initial report describing the controlled access to UHMW systems, this approach has been expanded to include k p Lower monomers enable more complex structures and utilize lower energy light sources. 13,29,30
[0249] The ability to initiate and mediate external polymerization using light is central to the synthesis of UHMW polymers via photoinitiators. Although light is a readily available and inexpensive external stimulus that allows for spatiotemporal control of chemical processes, scaling up photochemical intermittent reactions beyond the laboratory scale often presents significant problems. 31 According to the Beer-Lambert law, batch reactors are affected by light attenuation as the reactor size increases. 32 Therefore, continuous flow reactors have been extensively investigated as a method to scale up controlled photopolymerization using various RDRP methods. 33–42 In addition to more efficient light penetration, the higher surface area to volume ratio in tubular reactors provides other benefits over batch reactors, such as uniform heat transfer and rate enhancement of photochemical processes. 43 While the synthesis of UHMW polymers via photoinitiator polymerization could benefit from translation to tubular reactors, these polymerizations reach gel-like viscosities at high conversions, posing challenges for continuous flow. 44 Wang and his colleagues overcame these high viscosity issues by dispersing aqueous polymer droplets in n-octane, which allowed them to obtain polymers with molecular weights exceeding 10 6g / mol of polyacrylamide without clogging. 45 However, the RDRP method was not used in this system, limiting the access to more advanced polymer structures. Chen and colleagues used a similar surfactant-free droplet flow method to polymerize various medium molecular weight acrylates (ca. 4 g / mol). 46 Furthermore, although both approaches successfully reduce the high viscosities reached during concentrated solution polymerization, special reactor designs are required to achieve droplet flow conditions.
[0250] One approach to reduce polymerization viscosity is multiphase polymerization, where the polymerization sites are dispersed as droplets in an immiscible continuous phase. We recently reported an inverse miniemulsion (IME) batch system that enables the synthesis of well-controlled UHMW polymers using photoinitiator polymerization. Appropriate selection of emulsion variables, such as surfactant loading and stabilizer concentration, was optimized to produce uniformly dispersed particles with a diameter of approximately 130 nm. 47 The polymerization of N,N-dimethylacrylamide (DMA) mediated by various thiocarbonylthio-based photoinitiator compounds was achieved in a controlled manner to reach a temperature of more than 10 6 Importantly, the macroscopic viscosity of this UHMW IME polymerization is roughly equal to the viscosity of the cyclohexane continuous phase and remains constant as the polymerization proceeds. In contrast, the viscosity of UHMW solution polymerization increases by four orders of magnitude during polymerization due to entanglement of ultrahigh chain length polymers, making conversion to continuous flow reactors challenging. 44 We hypothesized that dispersed IME UHMW polymerization would provide a route to the synthesis of well-controlled UHMW polymers in a continuous flow.
[0251] In this paper, we describe the controlled synthesis of UHMW polymers by a continuous flow process under IME conditions using a variety of acrylamide-based monomers and a water-soluble trithiocarbonate iniferter. Due to the high surface area to volume ratio provided by the tubular reactor geometry, UHMW can be achieved in less than 1 hour, allowing for the rapid synthesis of a range of molecular weights (ca. 4 -10 6 ). In addition, switching to a continuous flow could help improve the scalability and industrial applicability of UHMW polymers synthesized by photoinitiators, which could facilitate their application in areas such as photonic materials, coatings or flocculants. 48-49
[0252] Results and Discussion
[0253] We initially investigated the synthesis of UHMW N,N-dimethylacrylamide (DMA) in a tubular flow reactor. A fluoropolymer tube was wrapped around an aluminum cylinder and placed inside an aluminum cylinder lined with a 365 nm UV LED (1 mW / cm 2 ) in an aluminum bucket. Before adding Span-60 and cyclohexane, an emulsion ( Figure 2.1A The resulting emulsion was sonicated, degassed, drawn into a syringe, and connected to the flow reactor via a syringe pump. The total exposure time to UV radiation was 1 h, and the ratio of monomer to photoinitiator was 10,000:1. The resulting polymer reached near quantitative conversion, and gel permeation chromatography (GPC) characterization showed consistent with the theoretical molecular weight (M n,理论值 :1.0×10 6 g / mol,M n,GPC :1.10×10 6 g / mol). A similar batch polymerization was carried out in a glass bottle for 1 hour with the same monomer / iniferter ratio. At the same monomer concentration, the batch reaction only achieved about 50% conversion (M) in the same time. n,理论值 :5.0×10 5 g / mol,M n,GPC :4.9×10 5 g / mol)( Figure 2.1B The increase in the aggregation rate is reflected in the pseudo-first-order rate diagram, where the apparent propagation rate constant (k p,app ) is increased relative to bath aggregation ( Figure 2.1C Junkers and co-workers previously reported similar rate increases in continuous flow compared to batch processes, which could be attributed to the increased surface area to volume ratio in tubular reactors. 43 This enhanced polymerization rate suggests that this approach shows promise in synthesizing polymer libraries with a variety of functionalities and molecular weights in a rapid manner.
[0254] To ensure that polymerization control is maintained despite the increase in polymerization rate, we studied the kinetics of IME polymerization targeting UHMW in flow. Emulsions prepared in the same manner as in the previous flow experiments were subjected to the same polymerization conditions; however, the reactor tube was divided into four equal parts to allow the collection of polymerization aliquots every 15 minutes of retention time. Linear pseudo-first-order kinetics indicated that the free radical concentration remained constant during the polymerization ( Figure 2.2A). Importantly, this indicates that the sulfur-centered radical products of PI homolysis do not leave the water droplet during the polymerization process, which would be seen as a negative deviation from linear behavior. In addition, although the optical transparency of the emulsion solution changes during the polymerization, sufficient light intensity is maintained throughout the polymerization process to mediate consistent homolysis of PI. Previous studies have found that performing polymerization under laminar flow can improve the dispersibility of continuously obtained polymer samples. 50 Furthermore, the sliding and spreading of miniemulsion droplets along the fluoropolymer tube walls have been shown to exacerbate this problem. 51 However, in our system, during the flow polymerization, the molecular weight obtained by GPC was in good agreement with the theoretical molecular weight calculated from the monomer conversion (Figure 2.3). The dispersity of the final polymer remained below 1.3, which is comparable to that of the polymerization carried out batchwise, indicating that the fluid dynamics of this reactor are suitable for obtaining low dispersity polymer samples in the UHMW state.
[0255] Dispersion particle size and stability are key parameters for IME polymerization. The emulsion is placed under high shear conditions (such as ultrasonic treatment) to form fine emulsion particles with a diameter of about 50-500nm. 44 After sonication but before polymerization, these particles undergo detrimental processes such as Ostwald ripening and agglomeration, which increase particle size and dispersibility. 52 To determine whether tubular flow conditions accelerate any adverse processes in the miniemulsion particles compared to batch reactions, we investigated particle stability in batch and flow on a time scale relevant to IME polymerization by assessing particle size changes over time using dynamic light scattering (DLS). First, the emulsion mixture was sonicated and the particle size was immediately measured by DLS ( Figure 2.4). The solution was then transferred to two sealed vials (stirred with a magnetic stirring bar and a static stirrer, respectively) and moved into a syringe placed in a syringe pump. The flow conditions were similar to those used in the previous polymerization process (1 hour retention time), and an aliquot was taken from the batch conditions after 1 hour. In both cases, the solution was not subjected to UV irradiation to prevent any stabilization of the particles obtained during the polymerization. After one hour, DLS analysis of the particles showed a slight increase in the average size of the particles due to the maturation of the emulsion, but in both cases, the batch and flow were comparable, indicating that there was no significant difference in the droplet behavior between the batch and flow. In addition, we tried to ensure that the pre-polymerized emulsion in the syringe was stable enough, because changes in the emulsion system before injection into the reactor may affect the molecular weight distribution of the polymer obtained after multiple retention times. The polymerization was carried out in the flow state under UV irradiation, and the resulting polymer droplets were analyzed by DLS method at different retention times. Satisfactorily, the samples obtained after two and four full retention times (1 hour retention time, samples collected at 2 hours and 4 hours) showed almost the same particle size distribution and dispersity as the pre-polymerized emulsion. These results indicate that the destabilization time of the miniemulsion particles is much longer than the retention time of the reaction. Therefore, for this scale of UHMW IME process, ultrasonication produces sufficiently stable particles to obtain a well-controlled distribution of UHMW polymer in the flow.
[0256] Table 1. Preparation of ultrahigh molecular weight polymers by photoinitiator polymerization under inverse miniemulsion conditions
[0257]
[0258] With this successful method for synthesizing UHMW polymers in a continuous manner established, we began to explore the accessible range of molecular weight, photoinitiator, and monomer selection (Table 1). Although approximately 10 6 g / mol target molecular weight, but more than 1.5×10 6 g / mol molecular weight remains challenging. For example, despite complete monomer conversion, 6 The target molecular weight is still 1.53×10 6 g / mol of polymer sample. This limitation has also been recorded in batch reactions and has been attributed to chain transfer events. 47Nevertheless, a wide range of molecular weights can be synthesized in a continuous flow simply by varying the ratio of monomer to iniferter. In this case, the amount of monomer was kept constant to ensure similar dispersed particle volumes, and only the catalyst loading was varied. The properties of the trithiocarbonates varied, and UHMWPDMA was also obtained using 2-(ethylthiocarbonylthiothio)propionic acid (PI 2), demonstrating that this approach can be used with a wide range of water-soluble photoinitiators. Finally, the monomer range was expanded to include 4-acryloylmorpholine (NAM), with results comparable to those for UHMW IME polymerization of DMA. We anticipate that this approach will be applicable to most water-soluble, high-k photoinitiator-polymerizable polymers. p Vinyl monomer.
[0259] It is worth noting that one-pot chain extension of UHMW solution polymerization is challenging because the high viscosity restricts the homogeneous diffusion of other monomers into the macroinitiator solution. However, UHMW IME polymerization allows for simple chain extension because the added water-soluble monomers preferentially partition into the polymer droplets and can subsequently be incorporated into the block copolymer. 47 Combined with photoinitiator polymerization, this feature of IME polymerization can easily obtain UHMW block copolymers. We utilized this method to evaluate chain end retention under IME conditions performed in flow. PDMA was synthesized in flow and collected in vials. To this emulsion, DMA in phosphate buffer was added and the polymer droplets were allowed to swell. Upon chain extension under batch conditions, the GPC curve of the PDMA polymer synthesized in flow clearly shifted to lower retention times, indicating that the polymer synthesized in flow maintained good chain end fidelity. While this semi-batch process can allow for the rapid synthesis of macroinitiator libraries in flow and subsequent chain extension in batch, a fully continuous process for the synthesis of block copolymers via IME in flow remains challenging because commercially available in-line static mixers do not provide sufficient mixing time for additional monomer to partition into polymer droplets, resulting in macroscopic phase separation within the reactor tube. We envision that these challenges can be overcome with more sophisticated reactor designs, allowing for the flow synthesis of multi-block copolymers.
[0260] In summary, the method described in this paper provides a route to synthesize UHMW polymers in a continuous manner. Due to the more efficient light penetration in the tubular reactor, we have demonstrated that molecular weights above 10 6Controlled polymers of 50 g / mol are achieved faster in flow than in batch while maintaining polymerization control and chain end fidelity. DLS experiments confirm that IME particle size is stable in flow on the time scale of laboratory-scale synthesis of UHMW polymers. Overall, this method of synthesizing UHMW polymers in continuous flow provides a way to more easily access a wider range of UHMW polymers (e.g., different functionalities, functional group densities, or molecular weight distribution shapes) by constructing more complex tubular reactor geometries. We anticipate that the continuous synthesis of controlled UHMW polymers will not only accelerate the application research of UHMW materials in fields such as biomaterials or photonic polymer materials, but will also contribute to the ultimate promotion of industrially relevant UHMW polymer materials.
[0261] References for Example 2:
[0262] (1) Zhou, L.; Triozzi, A.; Figueiredo, M.; Emrick, T. Fluorinated Polymer Zwitterions: Choline Phosphates and Phosphorylcholines. ACS Macro Lett. 2021, 10, 1204–1209.
[0263] (2) Hill, MR; Carmean, RN; Sumerlin, BS Expanding the Scope of RAFT Polymerization: Recent Advances and New Horizons. Macromolecules 2015, 48, 5459–5469.
[0264] (3)Matyjaszewski,K.;Spanswick,J.Controlled / Living RadicalPolymerization.Mater.Today 2005,8,26–33.
[0265] (4)Oliver, S.; Zhao, L.; Gormley, AJ; Chapman, R.; Boyer, C. Living in the Fast Lane-High Throughput Controlled / Living Radical Polymerization. Macromolecules 2019, 52, 3–23.
[0266] (5)Kowalewski,T.;Tsarevsky,N.V.;Matyjaszewski,K.Nanostructured CarbonArrays from Block Copolymers of Polyacrylonitrile.J.Am.Chem.Soc.2002,124,10632–10633.
[0267] (6)Torres,R.M.;Sun,M.;Yuan,R.;Abdelrahman,M.;Guo,Z.;Kowalewski,T.;Matyjaszewski,K.;Leduc,P.R.;Litster,S.Fe-Doped Copolymer-Templated Nitrogen-Rich Carbon as a PGM-Free Fuel Cell Catalyst.ACS Appl.Energy Mater.2021,2021,9653–9663.
[0268] (7)Korpusik,A.B.;Tan,Y.;Garrison,J.B.;Tan,W.;Sumerlin,B.S.Aptamer-Conjugated Micelles for Targeted Photodynamic Therapy Via PhotoinitiatedPolymerization-Induced Self-Assembly.Macromolecules 2021,54,7354–7363.
[0269] (8)Siegwart,D.J.;Oh,J.K.;Matyjaszewski,K.ATRP in the DesignofFunctional Materials for BiomedicalApplications.Prog.Polym.Sci.2012,37,18.
[0270] (9)Sumerlin,B.S.;Neugebauer,D.;Matyjaszewski,K.Initiation Efficiencyin the Synthesis of Molecular Brushes by Grafting from via Atom TransferRadical Polymerization.Macromolecules 2005,38,702–708.
[0271] (10)Allison-Logan,S.;Karimi,F.;Sun,Y.;McKenzie,T.G.;Nothling,M.D.;Bryant,G.;Qiao,G.G.Highly Living Stars via Core-First Photo-RAFTPolymerization:Exploitation for Ultra-High Molecular Weight StarSynthesis.ACS Macro Lett.2019,8,1291–1295.
[0272] (11)Wenn,B.;Martens,A.C.;Chuang,Y.M.;Gruber,J.;Junkers,T.EfficientMultiblock Star Polymer Synthesis from Photo-Induced Copper-MediatedPolymerization with up to 21 Arms.Polym.Chem.2016,7,2720–2727.
[0273] (12)Gao,H.;Matyjaszewski,K.Synthesis of Star Polymers by a New“Core-First”Method:Sequential Polymerization of Cross-Linker andMonomer.Macromolecules 2008,41,1118–1125.
[0274] (13)Allison-Logan,S.;Karimi,F.;Sun,Y.;McKenzie,T.G.;Nothling,M.D.;Bryant,G.;Qiao,G.G.Highly Living Stars via Core-First Photo-RAFTPolymerization:Exploitation for Ultra-High Molecular Weight StarSynthesis.ACS Macro Lett.2019,8,1291–1295.
[0275] (14)Garrison,J.B.;Hughes,R.W.;Young,J.B.;Sumerlin,B.S.PhotoinducedSET to Access Olefin-Acrylate Copolymers.Polym.Chem.2022,13,982–988.
[0276] (15)Garrison,J.B.;Hughes,R.W.;Sumerlin,B.S.Backbone Degradation ofPolymethacrylates via Metal-Free Ambient-Temperature Photoinduced Single-Electron Transfer.ACS Macro Lett.2022,441–446.
[0277] (16)Gody,G.;Maschmeyer,T.;Zetterlund,P.B.;Perrier,S.Exploitation ofthe Degenerative Transfer Mechanism in RAFT Polymerization for Synthesis ofPolymer of High Livingness at Full Monomer Conversion.Macromolecules 2014,47,639–649.
[0278] (17)Truong,N.P.;Dussert,M.V.;Whittaker,M.R.;Quinn,J.F.;Davis,T.P.Rapid Synthesis of Ultrahigh Molecular Weight and Low PolydispersityPolystyrene Diblock Copolymers by RAFT-Mediated EmulsionPolymerization.Polym.Chem.2015,6,3865–3874.
[0279] (18)Xu,J.;Jung,K.;Atme,A.;Shanmugam,S.;Boyer,C.A Robust and VersatilePhotoinduced Living Polymerization of Conjugated and Unconjugated Monomersand Its Oxygen Tolerance.J.Am.Chem.Soc.2014,136,5508–5519.
[0280] (19)Rzayev,J.;Penelle,J.HP-RAFT:A Free-Radical PolymerizationTechnique for Obtaining Living Polymers ofUltrahigh MolecularWeights.Angew.Chemie Int.Ed.2004,43,1691–1694.
[0281] (20)Read,E.;Guinaudeau,A.;Wilson,D.J.;Cadix,A.;Violleau,F.;Destarac,M.Low Temperature RAFT / MADIX Gel Polymerisation:Access to Controlled Ultra-High MolarMass Polyacrylamides.Polym.Chem.2014,5,2202–2207.
[0282] (21)Simms,R.W.;Cunningham,M.F.High Molecular Weight Poly(ButylMethacrylate)by Reverse Atom Transfer Radical Polymerization in MiniemulsionInitiated by a Redox System.Macromolecules 2007,40,860–866.
[0283] (22)Percec,V.;Guliashvili,T.;Ladislaw,J.S.;Wistrand,A.;Stjerndahl,A.;Sienkowska,M.J.;Monteiro,M.J.;Sahoo,S.Ultrafast Synthesis ofUltrahigh MolarMass Polymers by Metal-Catalyzed Living Radical Polymerization of Acrylates,Methacrylates,and Vinyl Chloride Mediated by SET at 25℃.J.Am.Chem.Soc.2006,128,14156–14165.
[0284] (23)Huang,Z.;Chen,J.;Zhang,L.;Cheng,Z.;Zhu,X.ICARATRP ofAcrylonitrileunder Ambient and High Pressure.Polym.2016,Vol.8,Page 592016,8,59.
[0285] (24)Mao,B.W.;Gan,L.H.;Gan,Y.Y.Ultra High Molar Mass Poly[2-(Dimethylamino)Ethyl Methacrylate]via Atom Transfer RadicalPolymerization.Polymer(Guildf).2006,47,3017–3020.
[0286] (25)Mueller,L.;Jakubowski,W.;Matyjaszewski,K.;Pietrasik,J.;Kwiatkowski,P.;Chaladaj,W.;Jurczak,J.Synthesis of High Molecular WeightPolystyrene UsingAGETATRP under High Pressure.Eur.Polym.J.2011,47,730–734.
[0287] (26)An,Z.100th Anniversary of Macromolecular Science Viewpoint:Achieving Ultrahigh Molecular Weights with Reversible Deactivation RadicalPolymerization.ACSMacro Lett.2020,9,350–357.
[0288] (27)Carmean,R.N.;Becker,T.E.;Sims,M.B.;Sumerlin,B.S.Ultra-HighMolecular Weights via Aqueous Reversible-Deactivation RadicalPolymerization.Chem 2017.
[0289] (28)Hartlieb,M.Photo-Iniferter RAFT Polymerization.Macromol.RapidCommun.2022,43,2100514.
[0290] (29)Carmean,R.N.;Sims,M.B.;Figg,C.A.;Hurst,P.J.;Patterson,J.P.;Sumerlin,B.S.Ultrahigh Molecular Weight Hydrophobic Acrylic and StyrenicPolymers through Organic-Phase Photoiniferter-Mediated Polymerization.ACSMacro Lett.2020,9,613–618.
[0291] (30)Lewis,R.W.;Evans,R.A.;Malic,N.;Saito,K.;Cameron,N.R.Ultra-FastAqueous Polymerisation of Acrylamides by High Power Visible Light DirectPhotoactivation RAFT Polymerisation.Polym.Chem.2017,9,60–68.
[0292] (31)Junkers,T.Precision Polymer Design in Microstructured FlowReactors:Improved Control and First Upscale at Once.Macromol.Chem.Phys.2017,218,1600421.
[0293] (32)Harper,K.C.;Moschetta,E.G.;Bordawekar,S.V;Wittenberger,S.J.ALaser Driven Flow Chemistry Platform for Scaling Photochemical Reactions withVisible Light.2019.
[0294] (33)Pan,X.;Tasdelen,M.A.;Laun,J.;Junkers,T.;Yagci,Y.;Matyjaszewski,K.Photomediated Controlled Radical Polymerization.Prog.Polym.Sci.2016,62,73–125.
[0295] (34)Corrigan,N.;Rosli,D.;Jones,J.W.J.;Xu,J.;Boyer,C.Oxygen Tolerancein Living Radical Polymerization:Investigation of Mechanism andImplementation in Continuous Flow Polymerization.Macromolecules 2016,49,6779–6789.
[0296] (35)Railian,S.;Wenn,B.;Junkers,T.Photo-Induced Copper-MediatedAcrylate Polymerization in Continuous-Flow Reactors.J.Flow Chem.2016,6,260–267.
[0297] (36)Chen,M.;Zhong,M.;Johnson,J.A.Light-Controlled RadicalPolymerization:Mechanisms,Methods,andApplications.Chem.Rev.2016,116,10167–10211.
[0298] (37)Ramsey,B.L.;Pearson,R.M.;Beck,L.R.;Miyake,G.M.PhotoinducedOrganocatalyzed Atom Transfer Radical Polymerization Using ContinuousFlow.Macromolecules 2017,50,2668–2674.
[0299] (38)Corrigan,N.;Trujillo,F.J.;Xu,J.;Moad,G.;Hawker,C.J.;Boyer,C.Divergent Synthesis of Graft and Branched Copolymers through SpatiallyControlled Photopolymerization in Flow Reactors.Macromolecules 2021,54,3430–3446.
[0300] (39)Judzewitsch,P.R.;Corrigan,N.;Trujillo,F.;Xu,J.;Moad,G.;Hawker,C.J.;Wong,E.H.H.;Boyer,C.High-Throughput Process for the Discovery ofAntimicrobial Polymers and Their Upscaled Production via FlowPolymerization.Macromolecules 2020,53,631–639.
[0301] (40)Reis,M.H.;Leibfarth,F.A.;Pitet,L.M.Polymerizations in ContinuousFlow:Recent Advances in the Synthesis of Diverse Polymeric Materials.ACSMacro Lett.2020,9,123–133.
[0302] (41)Chen,K.;Zhou,Y.;Han,S.;Liu,Y.;Chen,M.Main-Chain Fluoropolymerswith Alternating Sequence Control via Light-Driven Reversible-DeactivationCopolymerization in Batch and Flow.Angew.Chemie 2022,134,e202116135.
[0303] (42)Wang,J.;Hu,X.;Zhu,N.;Guo,K.Continuous Flow Photo-RAFT and Light-PISA.Chem.Eng.J.2021,420,127663.
[0304] (43)Rubens,M.;Latsrisaeng,P.;Junkers,T.Visible Light-InducedIniferter Polymerization of Methacrylates Enhanced by ContinuousFlow.Polym.Chem.2017,8,6496–6505.
[0305] (44)Genggeng,Q.;Jones,C.W.;Schork,F.J.RAFT Inverse MiniemulsionPolymerization of Acrylamide.Macromol.Rapid Commun.2007,28,1010–1016.
[0306] (45)Song,J.;Zhang,S.;Wang,K.;Wang,Y.Synthesis ofMillion MolecularWeight Polyacrylamide with Droplet Flow Microreactors.J.TaiwanInst.Chem.Eng.2019,98,78–84.
[0307] (46)Zhou,Y.;Gu,Y.;Jiang,K.;Chen,M.Droplet-Flow PhotopolymerizationAided by Computer:Overcoming the Challenges of Viscosity and Facilitating theGeneration of Copolymer Libraries.Macromolecules 2019,52,5611–5617.
[0308] (47)Olson,R.A.;Lott,M.E.;Garrison,J.B.;Davidson,C.L.G.;Trachsel,L.;Pedro,D.I.;Sawyer,W.G.;Sumerlin,B.S.Inverse Miniemulsion PhotoiniferterPolymerization for the Synthesis of Ultrahigh Molecular WeightPolymers.Macromolecules 2022,55,8451–8460.
[0309] (48)Hsu,S.Y.;Kayama,Y.;Ohno,K.;Sakakibara,K.;Fukuda,T.;Tsujii,Y.Controlled Synthesis of Concentrated Polymer Brushes with UltralargeThickness by Surface-Initiated Atom Transfer Radical Polymerization underHigh Pressure.Macromolecules 2020,53,132–137.
[0310] (49)Dao,V.H.;Cameron,N.R.;Saito,K.Synthesis of UHMW Star-Shaped ABBlock Copolymers and Their Flocculation Efficiency in High-Ionic-StrengthEnvironments.Macromolecules 2019,52,7613–7624.
[0311] (50)Reis,M.H.;Varner,T.P.;Leibfarth,F.A.The Influence of ResidenceTime Distribution on Continuous-Flow Polymerization.Macromolecules 2019,52,3551–3557.
[0312] (51)Russum,J.P.;Jones,C.W.;Schork,F.J.Impact of Flow Regime onPolydispersity in Tubular RAFT Miniemulsion Polymerization.AIChE J.2006,52,1566–1576.
[0313] (52)Asua,J.M.Miniemulsion Polymerization.Prog.Polym.Sci.2002,27,1283–1346.
[0314] It should be noted that ratios, concentrations, amounts, sizes, and other numerical data may be expressed in a range format herein. It should be understood that such a range format is used for convenience and brevity, and therefore, should be interpreted in a flexible manner as not only including the numerical values explicitly listed as limits of the range, but also including all individual numerical values or sub-ranges contained within the range, as if each numerical value and sub-range were explicitly listed. For illustration, the "range of about 0.1% to about 5%" should be interpreted as not only including the range of about 0.1% to about 5% explicitly listed, but also including individual ranges (e.g., 1%, 2%, 3% and 4%) and sub-ranges (e.g., 0.5%, 1.1%, 2.2%, 3.3% and 4.4%) within the specified range. In one embodiment, the term "about" may include traditional rounding according to numerical values and measurement techniques. In addition, the phrase "about 'x' to 'y'" includes "about 'x' to about 'y'".
[0315] It should be emphasized that the above-mentioned embodiments of the present disclosure are merely possible examples of implementation and are used to clearly understand the principles of the present disclosure. Various changes and modifications may be made to the above-mentioned embodiments of the present disclosure without departing substantially from the spirit and principles of the present disclosure. All of these modifications and changes are included within the scope of the present disclosure and are protected by the following claims.
Claims
1. A method for preparing a first water-soluble polymer, comprising: The main chain unit and at least one mucin binding unit are polymerized under reverse miniemulsion conditions using a photoinitiator to form a first water-soluble polymer.
2. The method of claim 1, wherein the method is a catalyst-free heterogeneous process mediated by low-intensity UV irradiation.
3. The method according to claim 1 or 2, wherein the method is a continuous process.
4. The method according to claim 1 or 2, wherein the method is a batch flow process.
5. The method of claims 1 to 4, wherein the multiphase inverse miniemulsion process comprises one of the following features: (1) the ability to prepare a high molecular weight water-compatible polymer in a low viscosity, high solids form; (2) forming a water-in-oil emulsion of an aqueous solution of a vinyl monomer in an inert hydrocarbon liquid organic dispersion medium; (3) forming droplets having a particle size in the range of 50-500 nanometers; or (4) free radical polymerization of the monomer in the dispersion medium to form polymer droplets.
6. The method of claims 1 to 5, wherein the first water-soluble polymer has a molecular weight of about 10 kDa to 10000 kDa.
7. The method of claims 1 to 6, wherein the first water-soluble polymer comprises a plurality of backbone units and at least one first type of mucin binding unit, wherein the backbone units comprise greater than 50% of the first water-soluble polymer based on molecular weight, wherein the first type of mucin binding unit comprises at most 50% of 1 unit of the first water-soluble polymer based on molecular weight, wherein the first type of mucin binding unit is functionalized such that the water-soluble polymer has a property that alters hydration, rheology, or both of a mucin polymer, a second water-soluble polymer, or a combination thereof, wherein the alteration in hydration, rheology, or both is achieved by mucoadhesion, mucoplasticity, mucoin integration, or a combination thereof.
8. The method of claim 1, wherein the backbone units comprise monomer units and copolymers comprising the monomer units, wherein the monomer units are selected from the group consisting of acrylamide monomers, methacrylamide monomers, acrylate monomers, methacrylate monomers, styrenic monomers, vinyl pyridine monomers, maleimide monomers, maleic anhydride derived monomers, vinyl ester monomers, vinyl ether monomers, vinyl amide monomers, vinyl amine monomers, vinyl halide monomers, substituted acrylamides, substituted methacrylamides, or derivatives of these monomers.
9. The method of claim 1, wherein the backbone unit comprises a monomer unit or a copolymer comprising the monomer unit, wherein the monomer unit is selected from the group consisting of acrylamide, N,N-dimethylacrylamide, N,N-dialkylacrylamide, N-alkylacrylamide, N,N-dialkylmethacrylamide, N-alkylmethacrylamide, poly(ethylene glycol)acrylate, poly(ethylene glycol)methacrylate, poly(ethylene glycol)acrylamide, and poly(ethylene glycol)methacrylamide.
10. The method of claim 1, wherein the backbone unit is N,N-dimethylacrylamide.
11. The method according to claim 1, wherein the backbone unit is N-hydroxyethyl acrylamide having the following structure: wherein n is 1 to 10, wherein R is a hydroxyl group, an amine group, a carboxylic acid group or a sulfonic acid group, wherein R' is C1 to C 18 Straight chain or branched chain alkyl.
12. The method of claim 1, wherein the first water-soluble polymer has a linear or non-linear structure selected from the group consisting of star, branched, hyperbranched, cyclic, schematically structured copolymers, or bottle brushes.
13. The method of claim 1, wherein the first water-soluble polymer has a non-linear structure selected from branched or hyperbranched.
14. The method of claim 1, wherein the mucin binding unit comprises a monomer unit or a copolymer comprising the monomer unit, wherein the monomer unit is selected from the group consisting of acrylic acid, methacrylic acid, 4-vinylbenzoic acid, 4-(acrylamide)phenylboronic acid, 3-(acrylamide)phenylboronic acid, 2-(acrylamide)phenylboronic acid, 4-vinylphenylboronic acid, 3-vinylphenylboronic acid, 2-vinylphenylboronic acid, ethyl 2-(pyridin-2-yldisulfonyl)methacrylate, ethyl pyridyldisulfide ... -(pyridin-2-yldisulfanyl)ethylacrylamide, ethyl 2-(pyridin-2-yldisulfanyl)methacrylate, or ethyl 2-(pyridin-2-yldisulfanyl)methacrylate, (4-((2-acrylamidoethyl)carbamoyl)-3-chlorophenyl)boric acid, (4-((2-acrylamidoethyl)carbamoyl)-3-fluorophenyl)boric acid, (4-((2-acrylamidoethyl)carbamoyl)-3-bromophenyl)boric acid, (4-((2-acrylamidoethyl)carbamoyl)-3-iodophenyl)boric acid, a monomer including one or more boronic acid groups, a monomer containing one or more disulfide bond-forming groups, or a derivative of any of them.
15. The method according to claim 1, wherein the mucin binding unit comprises a monomer unit or a copolymer comprising the monomer unit, wherein the monomer unit comprises a functional group selected from the group consisting of a boronic acid group, a carboxylate group, a carboxylic acid group, a hydrogen bonding group, a hydrophobic group, a 1,2-diol group, a 1,3-diol group, a group capable of forming a disulfide bond, or a derivative of any one thereof.
16. The method of claim 1, wherein the first water-soluble polymer comprises a second type of mucin-binding unit, wherein the second type of mucin-binding unit comprises a monomer unit or a copolymer comprising the monomer unit, wherein the monomer unit is selected from the group consisting of acrylic acid, methacrylic acid, 4-vinylbenzoic acid, 4-(acrylamide)phenylboronic acid, 3-(acrylamide)phenylboronic acid, 2-(acrylamide)phenylboronic acid, 4-vinylphenylboronic acid, 3-vinylphenylboronic acid, 2-vinylphenylboronic acid, ethyl 2-(pyridin-2-yldisulfonyl)methacrylate, ethyl pyridyldisulfide acrylate, pyridyldisulfide ethyl acrylamide, pyridyldisulfanyl (e.g., ethyl) methacrylamide, ethyl 2-(pyridin-2-yldisulfanyl)acrylate, 2-(pyridin-2-yldisulfanyl)ethylacrylamide, ethyl 2-(pyridin-2-yldisulfanyl)methacrylate, or ethyl 2-(pyridin-2-yldisulfanyl)methacrylate, (4-((2-acrylamidoethyl)carbamoyl)-3-chlorophenyl)boric acid, (4-((2-acrylamidoethyl)carbamoyl)-3-fluorophenyl)boric acid, (4-((2-acrylamidoethyl)carbamoyl)-3-bromophenyl)boric acid, (4-((2-acrylamidoethyl)carbamoyl)-3-iodophenyl)boric acid, a monomer comprising one or more boronic acid groups, a monomer containing one or more disulfide bond forming groups, or a derivative of any of them, wherein the first type of mucin binding unit is different from the second type of mucin binding unit.
17. The method of claim 16, wherein the first water-soluble polymer comprises a third type of mucin binding unit, wherein the third type of mucin binding unit comprises a monomer unit or a copolymer comprising a monomer unit, wherein the monomer unit is selected from the group consisting of acrylic acid, methacrylic acid, 4-vinylbenzoic acid, 4-(acrylamide)phenylboronic acid, 3-(acrylamide)phenylboronic acid, 2-(acrylamide)phenylboronic acid, 4-vinylphenylboronic acid, 3-vinylphenylboronic acid, 2-vinylphenylboronic acid, 2-(pyridin-2-yldisulfonyl)ethyl methacrylate, ethyl pyridyldithioacrylate, pyridyldithioethylacrylamide, pyridyldisulfanylmethacrylamide, ethyl 2-(pyridin-2-yldisulfanyl)acrylate, 2-(pyridin-2-yldisulfanyl)ethylacrylamide, 2-(pyridin-2-yldisulfanyl)ethylmethacrylate. Ester, or ethyl 2-(pyridin-2-yldisulfanyl)methacrylate, (4-((2-acrylamidoethyl)carbamoyl)-3-chlorophenyl)boronic acid, (4-((2-acrylamidoethyl)carbamoyl)-3-fluorophenyl)boronic acid, (4-((2-acrylamidoethyl)carbamoyl)-3-bromophenyl)boronic acid, (4-((2-acrylamidoethyl)carbamoyl)-3-iodophenyl)boronic acid, a monomer comprising one or more boronic acid groups, a monomer comprising one or more disulfide bond forming groups, or a derivative of any one thereof, wherein the first type of mucin binding unit is different from the second type of mucin binding unit, wherein the second type of mucin binding unit is different from the third type of mucin binding unit monomer, and the third type of mucin binding unit monomer comprises one or more pyridyl disulfide groups, or a derivative of any one thereof.
18. The method of claim 17, wherein the first type of mucin binding unit comprises from 1 functional unit to about 5% of the first water-soluble polymer based on molecular weight; wherein the second type of mucin binding unit comprises from 1 functional unit to about 5% of the first water-soluble polymer based on molecular weight; wherein the third type of mucin binding unit comprises from 1 functional unit to about 5% of the first water-soluble polymer based on molecular weight.
19. The method of claim 1, wherein the first type of mucin binding unit is located only at one or both ends of the first water-soluble polymer.
20. The method of claim 1, wherein the first water soluble polymer is a block copolymer.
21. The method of claim 1, wherein the first water-soluble polymer is a random copolymer.
22. The method of claim 1, wherein the first water-soluble polymer is a statistical copolymer.
23. The method of claim 1, wherein the first water-soluble polymer is an alternating copolymer.
24. The method of claim 1, wherein the first water-soluble polymer is a gradient copolymer.
25. The method of claim 20, wherein the block copolymer is an AB diblock copolymer or an ABA triblock copolymer, optionally wherein the mucin binding unit is isolated on the A block of the AB diblock copolymer or the A block of the ABA triblock copolymer.
26. The method of claim 1, wherein the first water-soluble polymer has the following chemical structure: wherein unit a is a backbone unit and m is greater than 50% of the first water-soluble polymer based on molecular weight, wherein unit b is a first type of mucin-binding unit and n is from 1 unit to about 50% of the first water-soluble polymer based on molecular weight, where unit a and unit b are different from each other, R a1 , R a2 , R a3 , R a4 , R b1 , R b2 , R b3 and R b4 Independently of each other, they can be H, -OR1, -NR1R2, -N + (R1)3, -N + (R1)2(R2), -N + (R1)(R2)(R3), -S(O)2R1, -S(O)2OR1, -S(O)2NR1R2, -NR1S(O)2R2, -NR1C(O)R2, -C(O)R1, -C(O)OR1, -C(O)NR1R2, -NR1C(O)OR2, -NR1C(O)NR1R2, -OC(O)NR1R2, -NR1S(O)2NR1R2, -C(O)NR1S(O)2NR1R2, catechol, boronic acid group and pyridyl disulfide group, wherein each R1, R2 and R3 are independently H or linear or branched C 1-18 Alkyl, and -C(O)OCH2CH2-OH, -C(O)OCH2CH2-N(CH3)2, -C(O)OCH2CH2-N + (CH3)3, -C(O)OCH2CH2-OSO3 – , -C(O)OCH2CH2-OSO3H, -C(O)OCH2CH2-SO3 – , -C(O)OCH2CH2-SO3H, and -C(O)N(H)C((CH3)2)CH2SO3 – , -C(O)N(H)C((CH3)2)CH2SO3H, Where X is C and Y is C.
27. The method of claim 1, wherein the first water-soluble polymer has the following chemical structure: wherein unit a is a backbone unit and m is greater than 50% of the first water-soluble polymer based on molecular weight, wherein unit b is a first type of mucin-binding unit and n is from 1 unit to about 50% of the first water-soluble polymer based on molecular weight, wherein unit c is a second type of mucin-binding unit and o is from 1 unit to about 50% of the first water-soluble polymer based on molecular weight, wherein unit a and unit b are different from each other, R a1 , R a2 , R a3 , R a4 , R b1 , R b2 , R b3 and R b4 Independently of each other, they can be H, -OR1, -NR1R2, -N + (R1)3, -N + (R1)2(R2), -N + (R1)(R2)(R3), -S(O)2R1, -S(O)2OR1, -S(O)2NR1R2, -NR1S(O)2R2, -NR1C(O)R2, -C(O)R1, -C(O)OR1, -C(O)NR1R2, -NR1C(O)OR2, -NR1C(O)NR1R2, -OC(O)NR1R2, -NR1S(O)2NR1R2, -C(O)NR1S(O)2NR1R2, catechol, boronic acid group and pyridyl disulfide group, wherein each R1, R2 and R3 are independently H or linear or branched C 1-18 Alkyl, and -C(O)OCH2CH2-OH, -C(O)OCH2CH2-N(CH3)2, -C(O)OCH2CH2-N + (CH3)3, -C(O)OCH2CH2-OSO3 – , -C(O)OCH2CH2-OSO3H, -C(O)OCH2CH2-SO3 – , -C(O)OCH2CH2-SO3H, and -C(O)N(H)C((CH3)2)CH2SO3 – , -C(O)N(H)C((CH3)2)CH2SO3H, wherein X is C, wherein Y is C, and wherein Z is C.
28. The method of claim 27, wherein unit a, unit b and unit c are different from each other.
29. The method of claim 1, wherein the first water-soluble polymer has the following chemical structure: wherein unit a is a backbone unit and m is greater than 50% of the first water-soluble polymer based on molecular weight, wherein unit b is a first type of mucin-binding unit and n is from 1 unit to about 50% of the first water-soluble polymer based on molecular weight, wherein unit c is a second type of mucin-binding unit and o is from 1 unit to about 50% of the first water-soluble polymer based on molecular weight, wherein unit d is a second type of mucin-binding unit and o is from 1 unit to about 50% of the first water-soluble polymer based on molecular weight, wherein unit a and unit b are different from each other, R a1 , R a2 , R a3 , R a4 , R b1 , R b2 , R b3 and R b4 Independently of each other, they can be H, -OR1, -NR1R2, -N + (R1)3, -N + (R1)2(R2), -N + (R1)(R2)(R3), -S(O)2R1, -S(O)2OR1, -S(O)2NR1R2, -NR1S(O)2R2, -NR1C(O)R2, -C(O)R1, -C(O)OR1, -C(O)NR1R2, -NR1C(O)OR2, -NR1C(O)NR1R2, -OC(O)NR1R2, -NR1S(O)2NR1R2, -C(O)NR1S(O)2NR1R2, catechol, boronic acid group and pyridyl disulfide group, wherein each R1, R2 and R3 are independently H or linear or branched C 1-18 Alkyl, and -C(O)OCH2CH2-OH, -C(O)OCH2CH2-N(CH3)2, -C(O)OCH2CH2-N + (CH3)3, -C(O)OCH2CH2-OSO3 – , -C(O)OCH2CH2-OSO3H, -C(O)OCH2CH2-SO3 – , -C(O)OCH2CH2-SO3H, and -C(O)N(H)C((CH3)2)CH2SO3 – , -C(O)N(H)C((CH3)2)CH2SO3H, wherein X is C, wherein Y is C, wherein Z is C, and wherein Q is C.
30. The method of claim 29, wherein unit a, unit b, unit c, and unit d are different from each other.
31. The method of claim 1, wherein the first water-soluble polymer has a molecular weight of about 100 kDa to 10,000 kDa.
32. A method for preparing a branched or hyperbranched first water-soluble polymer, comprising: A backbone unit and at least one mucin binding unit are polymerized to form a branched or hyperbranched first water-soluble polymer, wherein the branched or hyperbranched first water-soluble polymer has a molecular weight of about 10 kDa to 10,000 kDa, wherein the branched or hyperbranched first water-soluble polymer comprises a plurality of backbone units and at least one first type of mucin binding unit, wherein the backbone units comprise greater than 50% of the first water-soluble polymer based on molecular weight, wherein the first type of mucin binding unit comprises from 1 unit to at most 50% of the first water-soluble polymer based on molecular weight, wherein the first type of mucin binding unit is functionalized such that the water-soluble polymer has a property of altering hydration, rheology, or both of a mucin polymer, a second water-soluble polymer, or a combination thereof, wherein altering hydration, rheology, or both is achieved by mucoadhesion, mucoplasticity, mucoin integration, or a combination thereof.
33. The synthesis method according to claim 32, wherein the polymerization is cationic polymerization, anionic polymerization, ring-opening polymerization or coordination polymerization.
34. The synthesis method of claim 32, wherein the polymerization is free radical polymerization, conventional free radical polymerization, self-condensation vinyl polymerization (SCVP), reversible deactivation radical polymerization, reversible addition-fragmentation chain transfer (RAFT) polymerization, macromolecular design of xanthate exchange (MADIX) polymerization, photoinitiator polymerization, atom transfer radical polymerization (ATRP) or stable free radical polymerization (SFRP).
35. The synthesis method of claim 32, wherein when forming a branched or hyperbranched first water-soluble polymer, the backbone unit is the reaction product of a multifunctional water-soluble monomer and a water-soluble monofunctional unit, wherein the mole % of the multifunctional water-soluble monomer is less than 1% relative to the mole % of the monofunctional water-soluble monomer.
36. The synthesis method according to claim 35, wherein the monofunctional water-soluble monomer comprises one vinyl group or a functional group capable of linear polymerization, and wherein the multifunctional water-soluble monomer comprises two or more vinyl groups or functional groups capable of free radical polymerization.
37. The synthesis method according to claim 36, wherein the monofunctional water-soluble monomer is selected from N,N-dimethylacrylamide (DMA), N-hydroxyethylacrylamide (HEAm) or 2-methacryloyloxyethylphosphorylcholine (MPC).
38. The synthesis method according to claim 37, wherein the monofunctional water-soluble monomer is N,N'-methylenebisacrylamide.
39. The synthesis method of claim 32, wherein the polymerization is a self-condensation vinyl polymerization (SCVP) to form a hyperbranched first water-soluble polymer, wherein the backbone unit is the reaction product of a first initiating monomer and a second initiating monomer, wherein the first initiating monomer and the second initiating monomer comprise a vinyl group and a group capable of initiating polymerization or capable of being converted into a group capable of initiating polymerization.
40. The synthesis method according to claim 39, wherein the first and second initiating monomers are independently selected from the following structures: wherein X is CH3.
41. The synthesis method of claim 32, wherein the degree of branching (DB) of the hyperbranched first water-soluble polymer is greater than 0.4 but less than 1, or wherein the degree of branching (DB) of the branched first water-soluble polymer is greater than 0 but less than 0.
4.
42. The synthesis method according to claim 32, wherein the mucin binding unit comprises a monomer unit or a copolymer comprising the monomer unit, wherein the monomer unit comprises a functional group selected from the following: a boronic acid group, a carboxylate group, a carboxylic acid group, a hydrogen bonding group, a hydrophobic group, a 1,2-diol group, a 1,3-diol group, a group capable of forming a disulfide bond, or a derivative of any one thereof.
43. The synthesis method of claim 32, wherein the mucin binding unit is selected from the group consisting of acrylic acid, methacrylic acid, 4-vinylbenzoic acid, 4-(acrylamide)phenylboronic acid, 3-(acrylamide)phenylboronic acid, 2-(acrylamide)phenylboronic acid, 4-vinylphenylboronic acid, 3-vinylphenylboronic acid, 2-vinylphenylboronic acid, ethyl 2-(pyridin-2-yldisulfonyl)methacrylate, ethyl pyridinyldisulfide acrylate, pyridinyldisulfide ethylacrylamide, pyridinyldisulfide alkyl (e.g., ethyl)methacrylamide, ethyl 2-(pyridin-2-yldisulfide)acrylate, 2-(pyridin-2-yldisulfide) alkyl )ethyl acrylamide, ethyl 2-(pyridin-2-yldisulfanyl)methacrylate, ethyl 2-(pyridin-2-yldisulfanyl)methacrylate, (4-((2-acrylamidoethyl)carbamoyl)-3-chlorophenyl)boric acid, (4-((2-acrylamidoethyl)carbamoyl)-3-fluorophenyl)boric acid, (4-((2-acrylamidoethyl)carbamoyl)-3-bromophenyl)boric acid, (4-((2-acrylamidoethyl)carbamoyl)-3-iodophenyl)boric acid, a monomer including one or more boronic acid groups, a monomer containing one or more disulfide bond-forming groups, or a derivative of any one of them.
44. The synthetic method of claim 32, wherein the mucin binding unit comprises a functional group selected from the group consisting of a boronic acid group, a carboxylate group, a carboxylic acid group, a hydrogen bonding group, a hydrophobic group, a 1,2-diol group, a 1,3-diol group, and a group capable of forming a disulfide bond.
45. A composition comprising a first branched or hyperbranched water-soluble polymer having a molecular weight of about 10 kDa to 10,000 kDa, wherein the first branched or hyperbranched water-soluble polymer comprises a plurality of backbone units and at least one first type of mucin-binding unit, wherein the backbone units comprise greater than 50% of the first branched or hyperbranched water-soluble polymer based on molecular weight, wherein when forming the branched or hyperbranched first water-soluble polymer, the backbone units are the reaction product of a multifunctional water-soluble monomer and a water-soluble monofunctional unit, wherein the multifunctional water-soluble monomer has a molecular weight of about 10 kDa to about 10,000 kDa. The mole % relative to the mole % of the monofunctional water-soluble monomer is less than 1%, wherein the first type of mucin binding unit accounts for up to 50% of one unit of the first branched or hyperbranched water-soluble polymer based on molecular weight, wherein the first type of mucin binding unit is functionalized so that the first branched or hyperbranched water-soluble polymer has a property of causing the hydration, rheology, or both of the mucin polymer, the second water-soluble polymer, or a combination thereof to be altered, wherein the hydration, rheology, or both are altered by mucoadhesion, mucoadhesion, mucoadhesion, mucoadhesion, or a combination thereof.
46. The composition of claim 45, wherein the monofunctional water-soluble monomer comprises one vinyl group or a functional group capable of linear polymerization, and wherein the multifunctional water-soluble monomer comprises two or more vinyl groups or functional groups capable of free radical polymerization.
47. The composition of claim 46, wherein the monofunctional water-soluble monomer is selected from N,N-dimethylacrylamide (DMA), N-hydroxyethylacrylamide (HEAm) or 2-methacryloyloxyethylphosphorylcholine (MPC).
48. The composition of claim 47, wherein the monofunctional water-soluble monomer is N,N'-methylenebisacrylamide.
49. The composition of claim 45, wherein the hyperbranched first water-soluble polymer has a degree of branching (DB) greater than 0.4 but less than 1, or wherein the branched first water-soluble polymer has a degree of branching (DB) greater than 0 but less than 0.
4.
50. The composition of claim 45, wherein the first type of mucin binding unit is located only at one or both ends of the first water-soluble polymer.
51. The composition of claim 45, wherein the first water-soluble polymer is a block copolymer.
52. The composition of claim 45, wherein the first water-soluble polymer is a random copolymer.
53. The composition of claim 45, wherein the first water-soluble polymer is a statistical copolymer.
54. The composition of claim 45, wherein the first water-soluble polymer is an alternating copolymer.
55. The composition of claim 45, wherein the first water-soluble polymer is a gradient copolymer.
56. The composition of claim 55, wherein the block copolymer is an AB diblock copolymer or an ABA triblock copolymer, optionally wherein the mucin binding unit is isolated on the A block of the AB diblock copolymer or the A block of the ABA triblock copolymer.
57. The composition of claim 45, wherein the first water-soluble polymer has a molecular weight of about 100 kDa to 10,000 kDa.
58. A composition comprising a first branched or hyperbranched water-soluble polymer having a molecular weight of about 10 kDa to 10,000 kDa, wherein the first branched or hyperbranched water-soluble polymer comprises a plurality of backbone units and at least one first type of mucin binding unit, wherein the backbone units comprise greater than 50% of the first branched or hyperbranched water-soluble polymer based on molecular weight, wherein the backbone units are the reaction product of a first initiating monomer and a second initiating monomer, wherein the first initiating monomer and the second initiating monomer contain a vinyl group and a group capable of initiating polymerization or capable of being converted to a group capable of initiating polymerization, wherein the first type of mucin binding unit comprises at most 50% of one unit of the first branched or hyperbranched water-soluble polymer based on molecular weight, wherein the first type of mucin binding unit is functionalized such that the first branched or hyperbranched water-soluble polymer has a property of altering hydration, rheology, or both of a mucin polymer, a second water-soluble polymer, or a combination thereof, wherein altering hydration, rheology, or both is achieved by mucoadhesion, mucoplasticity, mucoin integration, or a combination thereof.
59. The composition of claim 58, wherein the first initiating monomer and the second initiating monomer are independently selected from the following structures: wherein X is CH3.
60. The composition of claim 58, wherein the hyperbranched first water-soluble polymer has a degree of branching (DB) greater than 0.4 but less than 1, or wherein the branched first water-soluble polymer has a degree of branching (DB) greater than 0 but less than 0.
4.
61. The composition of claim 58, wherein the first type of mucin binding unit is located only at one or both ends of the first water-soluble polymer.
62. The composition of claim 58, wherein the first water-soluble polymer is a block copolymer.
63. The composition of claim 58, wherein the first water-soluble polymer is a random copolymer.
64. The composition of claim 58, wherein the first water-soluble polymer is a statistical copolymer.
65. The composition of claim 58, wherein the first water-soluble polymer is an alternating copolymer.
66. The composition of claim 58, wherein the first water-soluble polymer is a gradient copolymer.
67. The composition of claim 66, wherein the block copolymer is an AB diblock copolymer or an ABA triblock copolymer, optionally wherein the mucin binding unit is isolated on the A block of the AB diblock copolymer or the A block of the ABA triblock copolymer.
68. The composition of claim 58, wherein the first water-soluble polymer has a molecular weight of about 100 kDa to 10,000 kDa.
69. A composition comprising a first water-soluble polymer having a molecular weight of about 10 kDa to 10,000 kDa, wherein the first water-soluble polymer comprises a plurality of backbone units and at least one first type of mucin binding unit, wherein the backbone units comprise greater than 50% of the first water-soluble polymer based on molecular weight, wherein the first type of mucin binding unit comprises at most 50% of 1 unit of the first water-soluble polymer based on molecular weight, wherein the first type of mucin binding unit is functionalized such that the first water-soluble polymer has a property that alters hydration, rheology, or both of a mucin polymer, a second water-soluble polymer, or a combination thereof, wherein the alteration in hydration, rheology, or both is achieved by mucoadhesion, mucoplasticity, mucoin integration, or a combination thereof; wherein the backbone unit comprises a monomer unit and a copolymer comprising the monomer unit, wherein the monomer unit is selected from substituted acrylamide or substituted methacrylamide, or wherein the mucin binding unit comprises a monomer unit or a copolymer comprising the monomer unit, wherein the monomer unit is selected from: (4-((2-acrylamidoethyl)carbamoyl)-3-chlorophenyl)boric acid, (4-((2-acrylamidoethyl)carbamoyl)-3-fluorophenyl)boric acid, (4-((2-acrylamidoethyl)carbamoyl)-3-bromophenyl)boric acid, (4-((2-acrylamidoethyl)carbamoyl)-3-iodophenyl)boric acid, a monomer comprising one or more boronic acid groups, a monomer containing one or more disulfide forming groups, or a derivative of any of these groups, The main chain unit is N-hydroxyethyl acrylamide having the following structure: wherein n is 1 to 10, wherein R is a hydroxyl group, an amine group, a carboxylic acid group or a sulfonic acid group, wherein R' is C1 to C 18 Straight chain or branched chain alkyl.
70. The composition of claim 69, wherein the backbone units comprise monomer units and copolymers comprising the monomer units, wherein the monomer units are selected from substituted acrylamide or substituted methacrylamide, and The mucin binding unit comprises a monomer unit or a copolymer comprising the monomer unit, wherein the monomer unit is selected from: (4-((2-acrylamidoethyl)carbamoyl)-3-chlorophenyl)boric acid, (4-((2-acrylamidoethyl)carbamoyl)-3-fluorophenyl)boric acid, (4-((2-acrylamidoethyl)carbamoyl)-3-bromophenyl)boric acid, (4-((2-acrylamidoethyl)carbamoyl)-3-iodophenyl)boric acid, a monomer comprising one or more boronic acid groups, a monomer containing one or more disulfide forming groups, or a derivative of any of these groups.
71. The composition of claim 69, wherein the backbone units comprise monomer units and copolymers comprising the monomer units, wherein the monomer units are selected from substituted acrylamide or substituted methacrylamide, and The main chain unit is N-hydroxyethyl acrylamide having the following structure: wherein n is 1 to 10, wherein R is a hydroxyl group, an amine group, a carboxylic acid group or a sulfonic acid group, wherein R' is C1 to C 18 Straight chain or branched chain alkyl.
72. The composition of claim 69, wherein the first water-soluble polymer has a linear or non-linear structure selected from the group consisting of star, branched, hyperbranched, cyclic, schematically structured copolymers, or bottle brush.
73. The composition of claim 69, wherein the first type of mucin binding unit is located only at one or both ends of the first water-soluble polymer.
74. The composition of claim 69, wherein the first water-soluble polymer is a block copolymer.
75. The composition of claim 69, wherein the first water-soluble polymer is a random copolymer.
76. The composition of claim 69, wherein the first water-soluble polymer is a statistical copolymer.
77. The composition of claim 69, wherein the first water-soluble polymer is an alternating copolymer.
78. The composition of claim 69, wherein the first water-soluble polymer is a gradient copolymer.
79. The composition of claim 78, wherein the block copolymer is an AB diblock copolymer or an ABA triblock copolymer, optionally wherein the mucin binding unit is isolated on the A block of the AB diblock copolymer or the A block of the ABA triblock copolymer.
80. The composition of claim 69, wherein the first water-soluble polymer has a molecular weight of about 100 kDa to 10,000 kDa.